Method of manufacturing an outsole component for an article of footwear
The manufacturing of outsole parts through a combination process of polymer hydrogel materials and molds solves the problem of dirt accumulation, improves adhesion friction and durability, and simplifies the manufacturing process.
Patent Information
- Application Number
- CN202111194091.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-08-01
- Filing Date
- 2018-08-01
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2038-08-01
AI Technical Summary
Existing outsole parts are prone to accumulate dirt when used in unpaved surfaces, affecting adhesion friction and comfort.
The outsole components are manufactured using polymer hydrogel materials, and the outsole components with high adhesion friction and anti-fouling accumulation are formed by providing a combined process of film components, molds and polymer materials.
Reduces dirt accumulation, improves durability and manufacturing efficiency of outsole components, reduces waste generation, and simplifies manufacturing processes.
Smart Images

Figure CN113968035B_ABST
Abstract
Description
[0001] This application is a divisional application of an application with an application date of August 1, 2018, application number 201880050672.X, and invention name “Method for manufacturing an outsole component for footwear articles”.
[0002] This application claims priority to U.S. Provisional Application No. 62 / 539,720, filed on August 1, 2017, the entire contents of which are incorporated herein by reference.
[0003] field
[0004] The present disclosure relates generally to articles of footwear. More specifically, the present disclosure relates to the manufacture of outsole components, which may include a complete outsole unit, that may be incorporated into articles of footwear, such as those used under conditions that favor the accumulation of dirt on the outsole. background
[0005] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.
[0006] Various types of footwear are often used in a variety of activities, including outdoor activities, military applications, and competitive sports. The outsoles of these types of footwear are typically designed to provide traction on soft and smooth surfaces, such as unpaved surfaces including grass and dirt. For example, enhanced tread patterns, lugs, cleats or spikes (both integral and removable), and rubber formulations that provide improved traction under wet conditions have been used to increase the level of traction provided by the outsoles.
[0007] While these conventional means generally help to impart improved traction to footwear, when footwear is used on unpaved surfaces, the outsole of the shoe typically accumulates dirt (e.g., inorganic materials, such as mud, dirt, sand, and gravel, organic materials, such as grass, turf, and other vegetation, and combinations of inorganic and organic materials). In some cases, dirt can accumulate in the tread pattern (when a tread pattern is present), around and between the lugs (when the lugs are present), or on the shaft of the cleat, in the space surrounding the cleat, and in the gap areas between the cleats (when the cleat is present). The accumulation of dirt can weigh down the footwear and interfere with the traction between the outsole and the ground. Summary of the invention
[0008] This application provides the following:
[0009] 1). A method for manufacturing an outsole component for an article of footwear, the method comprising:
[0010] providing a membrane component comprising a first outwardly facing surface, the membrane component comprising a first layer compositionally comprising a polymeric hydrogel material, the first layer defining at least a portion of the first outwardly facing surface of the membrane component;
[0011] providing a mold having a molding surface;
[0012] placing the film component into the mold;
[0013] constraining the film member such that at least a portion of the first layer contacts the molding surface to form a constrained film member;
[0014] loading a second polymeric material into the mold having the constrained film member;
[0015] at least partially solidifying the loaded second polymeric material in the mold to produce an outsole component having an outermost surface including at least a portion of the first layer of the membrane component; and
[0016] The outsole component is removed from the mold.
[0017] 2). The manufacturing method according to 1), wherein the step of providing the film member comprises extruding or co-extruding a film comprising the polymer hydrogel material.
[0018] 3). The manufacturing method according to 1) or 2), wherein the film component further comprises a backing layer operably connected to the first layer, the backing layer compositionally comprising a third polymer material.
[0019] 4). The manufacturing method according to any one of 1) to 3), wherein the film component is placed or constrained in the mold so that less than 85% of the total molding surface area of the mold is contacted by the film component.
[0020] 5). A manufacturing method according to any one of 1) to 4), wherein the method further comprises maintaining the film part at a temperature in the range of about 10°C (C) to about 80°C during at least the steps of placing the film part into the mold and constraining the film part.
[0021] 6). The manufacturing method according to 3), wherein the step of providing the membrane component comprises:
[0022] providing the third polymer material;
[0023] providing the polymer hydrogel material;
[0024] forming a layered film comprising a first layer of a polymer hydrogel material and a backing layer comprising the third polymer material using a coextrusion process or a lamination process; and
[0025] The layered film is cut to form the film member.
[0026] 7). A manufacturing method according to any one of 1)-6), wherein the method further comprises providing one or more traction friction elements, wherein the one or more traction friction elements are integrally formed with or operably connected to the molded outsole component, or a combination thereof.
[0027] 8). The manufacturing method according to 7), wherein the method further comprises adding a preformed traction friction element or a preformed accessory for a traction friction element to the mold before loading the second polymer material into the mold.
[0028] 9). The manufacturing method according to 7) or 8), wherein providing the membrane component comprises configuring the membrane component to fit between or around the one or more traction friction elements.
[0029] 10). A manufacturing method according to any one of 1) to 9), wherein the step of providing the film component comprises die-cutting the film using a flatbed printer, a rotary printer, a solid engraving mold, an adjustable mold, a magnetic plate tool, a punching die or a combination thereof to form the film component.
[0030] 11). A manufacturing method according to 7) or 8), wherein the step of providing the membrane component comprises: cutting one or more holes or gaps in a portion of the membrane component corresponding to the position of the one or more adhesion friction elements, or shaping a portion of the membrane component to avoid the position of one or more adhesion friction elements, or both cutting and shaping the membrane component.
[0031] 12). The production method according to any one of 1) to 11), wherein the second polymer material is a thermoplastic polymer material.
[0032] 13). The manufacturing method according to 3) or 6), wherein the third polymer material is a thermoplastic polymer material.
[0033] 14). A manufacturing method according to any one of 1) to 13), wherein the step of constraining a portion of the first layer against the molding surface comprises using a vacuum, using one or more retractable pins, or using both a vacuum and one or more retractable pins.
[0034] 15). A manufacturing method according to any one of 1) to 14), wherein placing the film part in the mold and / or constraining a portion of the first layer of the film part against a portion of the molding surface includes bending or curving the film part to conform to the curvature of the molding surface while maintaining the film part at a temperature in the range of about 10°C to about 80°C.
[0035] 16). The manufacturing method according to any one of 1) to 15), wherein the polymer hydrogel material comprises a polymer or copolymer of polyurethane, polyurea, polyester, polycarbonate, polyetheramide, addition polymer of ethylenically unsaturated monomers and any combination thereof.
[0036] 17). An outsole component for a footwear article, the outsole component comprising the outsole component manufactured according to any one of 1) to 16).
[0037] 18) An outsole component for a footwear article, the outsole component comprising:
[0038] The surface that touches the ground;
[0039] at least one membrane member having a first surface, a second surface opposite the first surface, and an outer perimeter, the membrane member compositionally comprising a polymer hydrogel material defining at least a portion of the first surface of the membrane member and at least a portion of the ground contacting surface of the outsole member;
[0040] a second polymeric material operably attached to the second surface of the film component and the entire outer perimeter of each of the one or more film components; and
[0041] one or more traction elements;
[0042] Wherein the at least one membrane member is fitted between or around the one or more traction friction elements.
[0043] 19) The outsole component of 18), wherein the one or more traction friction elements include a ground contacting surface, and the ground contacting surface of the one or more traction friction elements does not contain the polymer hydrogel material of the membrane component.
[0044] 20). An article of footwear comprising the outsole component according to any one of 17) to 19). BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order that the present disclosure may be better understood, various forms thereof given by way of example will now be described with reference to the accompanying drawings, in which:
[0046] Figure 1 is a flow chart describing a method of manufacturing an outsole or a component of an outsole according to aspects of the present disclosure;
[0047] Figure 2A are bottom side views of various outsole components formed according to aspects of the present disclosure;
[0048] Figure 2B are bottom side views of various outsole components formed according to aspects of the present disclosure;
[0049] Figure 3A is a bottom side view of an exterior surface of an outsole having traction elements according to aspects of the present disclosure;
[0050] Figure 3B is a perspective view of an article of footwear having an outsole with traction elements according to aspects of the present disclosure;
[0051] Figure 3C is a bottom side view of an exterior surface of an outsole having traction elements according to aspects of the present disclosure;
[0052] Figure 3D is a perspective view of an article of footwear having an outsole with traction elements according to aspects of the present disclosure; and
[0053] Figure 4 is a flow chart describing a method of manufacturing an article of footwear including an outsole formed according to aspects of the present disclosure.
[0054] The drawings described herein are for illustration purposes only and are not intended to limit the scope of the present disclosure in any way. Detailed Description
[0055] The present disclosure generally provides improved manufacturing processes for making outsole components using polymer hydrogel materials, and outsole components formed therefrom.
[0056] A prior method of manufacturing a component for an article of footwear comprising a hydrogel material defining a ground-contacting surface of an outsole component includes first forming a curved and shaped film component having a three-dimensional shape (e.g., a curved and shaped component having a depth at least 5 times greater than the thickness of the hydrogel film prior to thermoforming) using a thermoforming process by heating the film and pulling the film against a mold to conform a substantially planar portion of the hydrogel film to the curved shape of the outsole. Due to the configuration of the thermoforming equipment, a relatively large portion of the film is fed into the equipment (e.g., a 9 inch by 16 inch portion of the film) to thermoform a single component, resulting in a significant portion of the film portion being wasted as scrap. After the curved, shaped film component is cooled, excess film is then trimmed from the curved area of the periphery of the curved, shaped film component. The trimmed component is then placed in an injection mold, and the mold is then back injected with a thermoplastic material to form the outsole component. The process requires heating the hydrogel film twice—first during the thermoforming step, and then during the back injection step. The process also includes pulling the hydrogel film while heating it during the thermoforming process, producing thinning of the film in some areas of the part, such as in areas over or between traction elements, and some areas of excess material that ultimately becomes a significant portion of the waste. In addition, the process also requires trimming excess material from the perimeter of the thermoformed part in curved (i.e., not generally planar) areas, which requires either manually severing each thermoformed part or using complex, slow, and expensive automated cutting equipment capable of cutting in x, y, and z dimensions.
[0057] In contrast, the present method eliminates the need for a thermoforming step. Eliminating the thermoforming step reduces the thermal history to which the hydrogel material is exposed during manufacturing, which can result in reduced defects and increased durability in the finished product. The present method can also reduce the amount of waste material generated while allowing for the use of a simpler, faster, more cost-effective manufacturing process that can be more easily automated.
[0058] In one aspect, the present disclosure relates to a method for manufacturing an outsole component for an article of footwear, the method comprising: providing a membrane component including a first outward-facing surface, the membrane component including a first layer compositionally including a polymer hydrogel material, the first layer defining at least a portion of the first outward-facing surface of the membrane component; providing a mold having a molding surface; placing the membrane component into the mold; constraining the membrane component so that at least a portion of the first layer abuts a portion of the molding surface to form a constrained membrane component; loading a second polymer material into the mold having the constrained membrane component; at least partially solidifying the loaded second polymer material in the mold to produce an outsole component having an outermost surface that includes at least a portion of the first layer of the membrane component; and removing the outsole component from the mold. The present disclosure also relates to outsole components made according to these methods, and methods of making an article of footwear, the methods comprising providing an outsole component made according to these methods, providing an upper for the article of footwear, and securing the outsole component and the upper to each other such that the polymer hydrogel material of the outsole component defines a ground-facing surface of the article of footwear.
[0059] In another aspect, the present disclosure relates to an outsole component for an article of footwear, the outsole component comprising: a ground-contacting surface; at least one membrane component having a first surface, a second surface opposite the first surface, and an outer periphery, the membrane component compositionally comprising a polymer hydrogel material that defines at least a portion of the first surface of the membrane component and at least a portion of the ground-contacting surface of the outsole component; a second polymer material that is operably connected to the second surface of the membrane component and the entire outer periphery of each of the one or more membrane components; and one or more traction friction elements; wherein the at least one membrane component is assembled between or around the one or more traction friction elements.
[0060] Now that various aspects of the present disclosure have been generally described, additional details are provided. In one aspect, the method of the present disclosure begins with providing a film component that includes a first layer comprising a polymer hydrogel material. Instead of providing a portion of a hydrogel film that is thermoformed into a three-dimensional curved shape and then trimmed along the periphery of the thermoformed area to form a component that will be assembled within an injection mold, in the present method, the hydrogel film is provided as a film component. The film component is configured to be placed into the mold, that is, when the mold is closed, the film component does not extend beyond the periphery of the molding surface of the mold. The film component can be a pre-cut component, such as a substantially planar pre-cut film component. In a particular aspect, after the film of the film component has been formed, the film itself and the film component are not thermoformed or otherwise heated to above 80°C.
[0061] In some aspects, a portion of the film can be cut or stamped or molded to form the shape of the film component. The film can be an extruded or coextruded film, including an extruded layered film. In some aspects, the film component is configured to fit between or around one or more traction friction elements; that is, the periphery of the film component can be shaped to be placed between or around the base of the traction friction element, or one or more internal portions of the film component can be cut away, such as to form a hole or void, to be placed between or around the base of one or more traction friction elements, or both.
[0062] Next, a mold with a molding surface is provided, and the film component is placed in the mold so that a portion of the first layer of the film component (including the first layer of the polymer hydrogel material) contacts a portion of the molding surface of the mold. In the aspect that the film component is substantially planar and the molding surface is curved, the film component can be bent or curved so as to be assembled into the mold and contact the molding surface. However, it should be understood that this bending or bending will not include heating the film component to a temperature higher than 80 degrees Celsius (C). Next, the portion of the first layer contacting the molding surface is constrained against the portion of the molding surface, and the second polymer material is loaded into the mold at the same time. Constraining the first layer to partially abut against the molding surface reduces or eliminates the need for thermoforming the film component, and can prevent or reduce the leakage of the second polymer material between the film component and the molding surface during the loading step. In some aspects, the step of constraining the first layer to partially abut against the molding surface can include applying a vacuum to the film component, or applying a pin to the film component, or both. The loading step can include injection molding or pouring the second polymer material into the mold. After the second polymer material has at least partially solidified in the mold, the outsole component can be removed from the mold. Use of the process of the present disclosure avoids problems such as pulling and stretching the film during thermoforming, which can damage the film, resulting in scrap or waste material. Use of the process also reduces the "thermal history" of the film by limiting the number of times the hydrogel material is exposed to temperatures above 80° C. during manufacturing, which can cause material degradation. Use of the process can also reduce the amount of waste material compared to conventional thermoforming processes.
[0063] As used herein, the term "outsole element" refers to a component that can be combined with one or more additional components to form a complete outsole unit, as well as a complete outsole unit that can be attached to an upper to form an article of footwear. The terms polymer hydrogel material, hydrogel material, and hydrogel are used interchangeably throughout the disclosure to refer to the same element or material composition.
[0064] According to one aspect of a method of manufacturing an outsole component for an article of footwear according to the present disclosure, one or more flat membrane components are provided, the flat membrane components being formed of a layered film having a polymer material forming a backing layer and a polymer hydrogel material operably connected to the backing layer, such that the polymer hydrogel material defines an outwardly facing surface of the flat membrane component. A mold having a molding surface is then provided, and the flat membrane component is placed into the mold such that the polymer hydrogel layer of the layered film is in direct contact with at least a portion of the molding surface. A second polymer material is added to the mold such that the membrane component defines at least a portion of the outer surface of the outsole, wherein the hydrogel forms its outermost layer. During the addition of the second polymer material to at least a portion of the mold, the membrane component is held against the molding surface. The second polymer material solidifies in the mold; and the outsole or outsole component is then removed from the mold.
[0065] According to another aspect of the present disclosure, a method of manufacturing an article of footwear includes: providing an outsole component manufactured according to the method described above and further defined herein; providing an upper; and securing the outsole component and the upper to each other so that the polymer hydrogel material defines a ground-facing surface of the article of footwear.
[0066] According to another aspect of the present disclosure, an outsole component for an article of footwear includes one or more membrane components, wherein each membrane component has an outer perimeter, and the membrane of each membrane component includes a backing layer of a first polymer film and a polymer hydrogel material operably connected to the backing layer, so that the polymer hydrogel material defines a surface of the outsole component that contacts the ground. A second polymer material is operably connected to the backing layer and is operably connected to the entire outer perimeter of each of the one or more membrane components. The outsole component also includes one or more traction friction elements, wherein the one or more membrane components are configured to fit between or around the traction friction elements.
[0067] Outsole components formed in accordance with the teachings of the present disclosure can prevent or reduce the accumulation of dirt on their surfaces during use or wear on unpaved surfaces. As used herein, the term "dirt" includes one or more of a variety of materials that are typically present in the ground or on a playing surface that may otherwise adhere to an article (e.g., an exposed outsole of an article of footwear, etc.). Dirt can include, without limitation, inorganic materials such as mud, sand, dirt, and gravel; organic matter such as grass, turf, leaves, other vegetation, and excrement; and combinations of inorganic and organic materials, such as clay. In addition, dirt can include other materials such as pulverized rubber that may be present on or in an unpaved surface.
[0068] As will be appreciated by those skilled in the art, preventing or reducing dirt accumulation on footwear can provide many benefits. Preventing or reducing dirt accumulation on the outsole of footwear during wear on unpaved surfaces can also significantly affect the weight of the accumulated dirt that adheres to the outsole during wear, which reduces the fatigue caused to the wearer by the adhered dirt. Preventing or reducing dirt accumulation on the outsole can help maintain the traction during wear. For example, preventing or reducing dirt accumulation on the outsole can improve or maintain the performance of the traction elements on the surface facing the ground of the outsole during wear on unpaved surfaces. When worn while playing sports, preventing or reducing dirt accumulation on the outsole can improve or maintain the wearer's ability to manipulate sports equipment such as balls with footwear. In addition, preventing or reducing dirt accumulation on the outsole can make it easier to clean footwear after use.
[0069] The following description is merely exemplary in nature and is not intended to limit the present disclosure or its application or use. For example, several examples of tread patterns and traction friction elements are described throughout the present disclosure as combined outsoles or parts of outsoles in footwear articles manufactured and used according to the teachings contained herein to more fully illustrate their composition and use. It is within the scope of the present disclosure to combine and use such outsoles or parts of outsoles in footwear articles having different tread patterns and traction friction elements. Those skilled in the art will understand that throughout the specification, corresponding reference numerals represent similar or corresponding parts and features. Additional applicable fields will become apparent from the description provided herein.
[0070] As used herein, the terms "article of footwear" and "footwear" are intended to be used interchangeably to refer to the same article. Typically, the term "article of footwear" will be used first, and for ease of reading, the term "footwear" may be used subsequently to refer to the same article.
[0071] The outsole or the parts of the outsole for footwear articles manufactured according to the teaching of the present disclosure can be designed to be used for multiple purposes, such as sports, sports, military, work-related purposes, entertainment or leisure purposes. For example, footwear articles can be intended to be used outdoors on unpaved surfaces (partially or entirely), such as on the ground surface including one or more of grass, turf, gravel, sand, earth, clay, mud and the like. The surface can be a general outdoor surface or a sports performance surface (for example, American football (football) field / English football (soccer) field, golf course, baseball field, track and field, bicycle field, etc.). Footwear articles can be intended for indoor use, such as indoor sports (for example, indoor baseball field and indoor American football / English football game field with mud infield) carried out on dirt surface (dirtsurface). These footwear articles can optionally include traction friction elements (for example, lugs, anti-skid parts, studs (stud), sole nails (spike), etc.) to provide traction friction on a soft and smooth surface. Cleats, spikes and cleats are commonly included in footwear designed for use in sports such as football / soccer, golf, baseball and similar sports that are often played on unpaved surfaces. Lugs and / or enhanced tread patterns are commonly included in footwear, including boots designed for use in harsh outdoor conditions such as trail running, hiking and military use.
[0072] Reference Figure 1 , a method 1 for manufacturing an outsole component for an article of footwear includes providing 5 a flat film component, the flat film component including a first layer defining an outwardly facing surface of the flat film component, the first layer compositionally including, consisting of, or consisting essentially of a polymer hydrogel material. The polymer hydrogel material represents a first polymer material used in the process. The manufacturing method 1 also includes providing 10 a mold having a molding surface. The molding surface can have a predetermined shape for a desired outsole component. The flat film component is placed 15 into the mold so that a portion of the first layer contacts a portion of the molding surface. When necessary or desired, the flat film component can be bent or curved 13 so that it conforms to a curvature associated with the molding surface while maintaining the film component at a temperature in the range of about 10° C. to about 80° C.
[0073] According to the manufacturing method 1, a portion of the first layer is constrained or held against a portion of the molding surface while a second polymer material is loaded 20 into the mold so that the membrane component defines at least a portion of the first layer of the membrane component, forming the outermost layer of the outsole component. During the addition of the second polymer material to at least a portion of the mold, the membrane component is held 20 against the molding surface. The membrane component can be held in place using a holding mechanism. The second polymer material is allowed to at least partially solidify 25 to produce the outsole component, wherein a portion of the first layer serves as the outermost layer. The formed outsole component is then removed 30 from the mold. The molding steps 20, 25 can be completed within the scope of an injection molding or compression molding process, but are not limited thereto.
[0074] The step of placing the film component into the mold 15 so that a portion of the first layer contacts a portion of the molding surface includes placing the film component into the mold so that the first layer contacts a portion of the molding surface that is less than 85% of the total molding surface area of the mold. Optionally, the first layer contacts a portion of the molding surface that is less than 80% of the total molding surface area of the mold; alternatively, less than 75%; alternatively, between about 10% and about 80%.
[0075] As used herein, the total molded surface area corresponds to the surface area of the mold segment against which the layer is constrained. For example, the total surface area of a two-piece injection mold represents the total surface area of one half of the mold when the film component is constrained or held against that half during the molding operation.
[0076] In this manufacturing method 1, the molding steps 20, 25 associated with forming the outsole component are the only steps in the manufacturing method 1 that may expose the hydrogel to heat treatment. In other words, during the manufacturing method 1, the flat membrane component is maintained at a temperature in the range of about 10°C to about 80°C, except during the step of loading 20 the second polymer material into the mold, which includes after loading the second polymer material into the mold and at least partially solidifying 25 the second polymer material in the mold.
[0077] The step 20 of loading the mold with the second polymer material may include closing the mold and injecting the second polymer material into the closed mold using an injection molding process. The step 20 of loading the mold may also include loading the second polymer material into the mold, closing the mold before, during or after loading, and applying compression to the closed mold.
[0078] Although the laminar film is described as a flat part in the manufacturing method 1, the laminar film can be substantially planar or relatively planar, with a degree of curvature in a portion of the flat part or along one or more edges of the flat part. A greater degree of curvature can be incorporated into the flat part, for example during the molding steps 20, 25 as further defined herein. When desired, the flat film part can be optionally bent or curved to conform to the curvature 13 of the molding surface.
[0079] According to aspects of the present disclosure, the flat film component may be formed by an extrusion process, a coextrusion process, or a lamination process 2. When desired, the film component may include a backing layer formed of a third polymer material 8. The flat film component may be prepared by providing 3 a third polymer material; providing 7 a polymer hydrogel material; and forming a layered film 9 by a coextrusion process or a lamination process to provide a film component having a polymer hydrogel layer and a backing layer comprising a third polymer. The polymer hydrogel may be exposed to a heat treatment exceeding 80° C. during the extrusion process, coextrusion process, or lamination process for forming the layered film. Therefore, in this case, the flat film component is maintained at a temperature in the range of about 10° C. to about 80° C., except during the steps of forming the layered film 2, 9, adding the second polymer material to the mold 20, and after loading the mold with the second polymer material and at least partially solidifying the second polymer material in the mold 25.
[0080] When desired, the third polymer material may be at least partially cured 6, or optionally fully cured, prior to use in the outsole manufacturing method 1 or during the molding steps 20, 25 in the process. However, during the manufacturing process 1, the flat film component is not subjected to any other process steps, such as thermoforming or vacuum forming that exposes the flat component to high temperatures (i.e., heat treatment) that can form the flat component into a curved shape.
[0081] As used herein, the term "providing," such as for "providing an outer sole for a shoe," when recited in a claim, is not intended to require any specific delivery or receipt of the provided item. Instead, for the purposes of clarity and ease of reading, the term "providing" is used only to recite items that will be referred to in subsequent elements of the claim.
[0082] Still refer to Figure 1, the manufacturing method 1 may also include at least partially curing 29 the second polymer material. When desired, the second polymer material may be fully cured. For the purposes of the present disclosure, the term "partially cured" means an incidence of at least about 1%, optionally at least about 5%, of the total polymerization required to achieve substantially complete curing. The term "fully cured" is intended to mean substantially complete curing, wherein the degree of curing is such that the physical properties of the cured material do not significantly change upon further exposure to conditions that induce curing (e.g., temperature, pressure, presence of a curing agent, etc.).
[0083] For purposes of the present disclosure, the terms "about" and "substantially" are used herein with respect to measurable values and ranges due to expected variations known to those skilled in the art (eg, limitations and variability in measurements).
[0084] Still refer to Figure 1 , the layered film can be cut 11 to form a flat film portion configured to fit between or around one or more traction friction elements. When desired, a portion of the layered film can be configured 16 to fit between or around one or more traction friction elements by cutting one or more holes or gaps into the portion of the film to accommodate the traction friction elements, or by shaping the portion of the film to avoid one or more traction friction elements, or by both cutting the film and shaping the film. Those skilled in the art will understand the various ways or methods in which the layered film can be cut. One aspect of cutting the layered film is, without limitation, by using a die cutting operation that uses a flatbed press or a rotary press. Die cutting can be accomplished using a solid engraved die, an adjustable die, a magnetic plate tool, a dinking die, or a combination thereof.
[0085] Now refer to Figure 2A and Figure 2B , showing that in Figure 1 The layered film of the flat film component 50 after cutting 11 in the manufacturing method 1 of the present invention. The cutting step can be configured to provide one or more holes or voids (e.g., 55, 60) that fit around one or more traction friction elements and provide a substantially continuous region of the flat film along at least a portion of the outsole of the footwear. For example, referring to Figure 2B, one or more holes 55 may be cut or punched into the flat membrane, each hole 55 having a shape and size to accommodate a corresponding traction element, such that, for example, the traction element may extend through hole 55, or protrude from the outsole in an area generally corresponding to hole 55 in the membrane. Figure 2A , one or more contours or voids 60 can be formed at or near the edge of the formed membrane, each contour or void 60 having a shape and size to accommodate a corresponding traction friction element, so that, for example, the traction friction element can protrude from the outsole in an area generally corresponding to the void 60 in the membrane. In addition, configuring the membrane to fit between or around the traction friction elements can include cutting one or more holes in the flat portion to accommodate the traction friction elements, or shaping the flat portion to avoid the traction friction elements. According to these aspects, the traction friction elements of the outsole do not contain any hydrogel material.
[0086] Refer again Figure 1 The mold provided in step 10 for injection molding steps 20, 25 may include a molding surface, at least a portion of which is curved into a predetermined shape. The desired shape of the outsole or component of the outsole to be formed defines the degree of curvature associated with the molding surface. Thus, the molding surface is in the predetermined shape of the outsole component to be formed.
[0087] A portion of the first layer of the planar membrane component may be constrained or held 20 against the molding surface using a holding mechanism, which may include, but is not limited to, a vacuum, one or more retractable pins, or a combination thereof. During the molding steps 20, 25, at least a portion of the first layer of the planar membrane component is placed against the molding surface 15 so that after the second polymer material is added and after it cools or solidifies 25, the layered membrane takes the shape of the molding surface. In this configuration, the polymer hydrogel material in the first layer of the planar membrane component forms at least a portion of the outer surface of the outsole. According to some aspects, the polymer hydrogel material forms at least 80%, or at least 85%, of the outer surface of the outsole component.
[0088] Refer again Figure 2A and Figure 2B, illustrates aspects of an outsole component 65 formed via manufacturing method 1 to show the incorporation of a flat membrane component 50 into the outsole component 65. As illustrated, the outsole component 65 has a number of traction friction elements 70 formed therewith. The traction friction elements can be formed integrally with the outsole during molding steps 20, 25. In this case, the traction friction elements generally include a second polymer material or a third polymer material. According to these aspects, the flat membrane component 50 has been configured to include holes or voids 55, 60 that correspond to the locations of the traction friction elements 70, so that the traction friction elements 70 extend through or from areas of the outsole component 65 that correspond to the locations of the holes or voids 55, 60 (i.e., areas without hydrogel material).
[0089] Refer again Figure 1 , when desired, a fourth polymer material may be added 27 to the mold, at least a portion of the traction friction elements being formed from the fourth polymer material. Optionally, in some aspects, all of the traction friction elements may be formed from the fourth polymer material. When desired, the fourth material may be at least partially cured 29. The fourth polymer material may be a thermoplastic polymer material. When desired, the fourth polymer material may have the same or similar composition as the second polymer material or the third polymer material. The fourth polymer material may exhibit a greater degree of wear resistance than the second polymer material or the third polymer material.
[0090] According to some aspects, one or more of the traction friction elements may include elements that are separately added after the outsole is removed from the mold, such as snap-fit components, screw-on components, or combinations thereof. In these aspects, the separately added traction friction elements can be individually selected to include a material that is the same as the second polymer material, the third polymer material, or the fourth polymer material, or a material that is different from or substantially free of the second polymer material, the third polymer material, or the fourth polymer material. The separately added traction friction elements can be permanently or removably coupled to the outsole. When desired, such as Figure 1As shown in , before adding the second polymer material, one or more accessories can be placed 17 (A) into the mold to be formed with the outsole or outsole component. These accessories are configured to be connected with the traction friction elements added separately, such as snap-fit components or screw-on components. According to certain aspects, before adding the second polymer material, the pre-formed traction friction element tip can be placed 17 (B) into the mold to be formed with the outsole or outsole component. These pre-formed traction friction elements can be selected individually to include materials that are the same as the second polymer material, the third polymer material, or the fourth polymer material, or materials that are different from or substantially free of the second polymer material, the third polymer material, or the fourth polymer material.
[0091] Now refer to Figures 3A-3D , the one or more traction elements 70 disposed on the outer surface 75 of the outsole 65 may represent a tread pattern, lugs, cleats, spikes, studs, or a combination thereof. The number of traction elements 70 and the location or pattern of the traction elements located on the ground-facing surface or outer surface 75 of the outsole 65 may vary between different articles of footwear 80. The location and pattern of the traction elements may be predetermined to provide a necessary or desired effect or function.
[0092] According to another aspect of the present disclosure, an outsole component for an article of footwear includes one or more membrane components, wherein each membrane component has an outer perimeter, and the membrane of each membrane component includes a backing layer of a first polymer film and a polymer hydrogel material operably connected to the backing layer, so that the polymer hydrogel material defines the surface of the outsole component that contacts the ground. A second polymer material is operably connected to the backing layer and is operably connected to the entire outer perimeter of each of the one or more membrane components. The outsole component also includes one or more traction friction elements, wherein one or more membrane components are configured to be assembled between or around the traction friction elements. The traction friction element can have a surface that contacts the ground that does not include the membrane component. The membrane component can include a void having an inner perimeter, and the traction friction element passes through the void of the membrane component. When needed, the traction friction element can include a second polymer material, which is operably connected to the inner perimeter of the membrane component. The second polymer material can also define the surface of the traction friction element that contacts the ground.
[0093] Outsole 65 may be incorporated into article of footwear 80 (in Figure 3B and Figure 3D85 ), such that the outsole 65 is coupled to or attached to the upper 85. The upper 85 of the footwear 80 has a body that may be made of materials known in the art for making articles of footwear and is configured to receive the foot of a user. The upper 85 of the shoe 80 consists of all the components of the shoe above the outsole 65. The different components of the upper 85 may include a toe box; a heel counter; and an Achilles notch, to name a few. These components may be attached by stitching, or more likely molded as a single unit to which the outsole 65 is coupled.
[0094] Now refer to Figure 4 According to another aspect of the present disclosure, a method 100 of forming an article of footwear may include, consist of, or consist essentially of: providing or receiving 105 an upper; providing or receiving 110 an outsole component manufactured according to manufacturing method 1 as previously described and further defined herein; and coupling or fixing 115 the upper and outsole component together. When desired, the method may also include receiving 120 a midsole; and coupling 125 the midsole to the outsole component and / or the upper before coupling the outsole component to the upper, such that the midsole resides between the outsole component and the upper.
[0095] The method of forming the article of footwear 100 may also include at least partially curing 130 the second polymer material, the third polymer material, and / or the fourth polymer material used to make the outsole by the occurrence of one or more cross-linking mechanisms. Such cross-linking mechanisms may occur, for example, via a sulfur-based cross-linking process or a peroxide-initiated cross-linking process that results in the curing of the polymer material, or by exposing the polymer material to a concentration of actinic radiation for a period of time to at least partially cure the mixture.
[0096] When desired, the method 100 of forming an article of footwear may also utilize an adhesive, a primer, or a combination of both 135 to help secure or attach the outsole component to the upper and / or secure or attach the midsole to the upper or outsole. The adhesive or primer may include, but is not limited to, epoxy, polyurethane, acrylic, cyanoacrylate, silicone, or a combination thereof.
[0097] While not wishing to be bound by theory, it is believed that outsoles of articles of footwear formed in accordance with the present disclosure can provide compressive compliance and / or drainage of absorbed water when substantially wetted with water (including water containing dissolved, dispersed, or otherwise suspended materials). In particular, it is believed that compressive compliance of the wet surface composition of the component, drainage of liquid from the wet surface composition, or a combination thereof can disrupt the adhesion of dirt to the article components and / or the cohesion of dirt particles to each other.
[0098] This disruption of the adhesion and / or sticking of dirt is believed to be a mechanism that can prevent (or otherwise reduce) the accumulation of dirt on the outsole (due to the presence of the wet material), or at least allow the dirt to be removed with less effort (e.g., easier to wipe, brush, or otherwise physically remove). As will be appreciated by those skilled in the art, preventing the accumulation of dirt on the outsole can provide a number of benefits, such as preventing the accumulation of weight on an article of footwear.
[0099] As discussed above, the outer surface of the outsole component of the shoe manufactured by the method of the present disclosure includes a polymer hydrogel material that allows the material to absorb water. As used herein, the terms "takeup," "taking up," "uptake," "uptaking," and similar terms refer to the drawing of liquid (e.g., water) into the component from an external source, such as by absorption, adsorption, capillary action, or a combination thereof. In addition, as briefly mentioned above, the term "water" refers to an aqueous liquid, which can be pure water, or can be an aqueous carrier with smaller amounts of dissolved, dispersed, or otherwise suspended materials (e.g., particles, other liquids, and the like).
[0100] The ability of a polymer hydrogel material to absorb water and swell, along with the associated increase in compliance, can reflect its ability to prevent dirt accumulation during use of an article of footwear. For convenience, polymer hydrogel materials may be described hereinafter using the general term "hydrogel." As discussed above, when a hydrogel absorbs water (e.g., by absorption, adsorption, capillary action, etc.), the water absorbed by the hydrogel transforms the hydrogel from a dry, relatively rigid state to a relatively compliant, partially hydrated or fully saturated state. The presence of water on the surface of the hydrogel is believed to be one mechanism for reducing the adhesion of dirt to the material.
[0101] In addition, when the hydrated hydrogel experiences the application of compression or bending pressure, the volume of the hydrogel can be reduced and at least a portion of the water it absorbs can be discharged. This discharged water is believed to reduce or destroy the adhesion / adhesion of dirt particles on or at the surface of the outsole. In particular, it is believed that the compression compliance of the hydrated hydrogel material, the discharge of liquid from the hydrated hydrogel material, or a combination of the two, can destroy the adhesion of dirt on or at the outsole, or the adhesion of particles to each other, or can destroy both adhesion and adhesion. This destruction of the adhesion and / or adhesion of dirt is believed to be a mechanism responsible for preventing (or otherwise reducing) the accumulation of dirt on the outsole of footwear (due to the presence of wet material). As can be appreciated, preventing dirt from accumulating on the bottom of the footwear can improve the performance of the traction elements present on the outsole during wear on unpaved surfaces, can prevent the footwear from gaining weight due to dirt that accumulates during wear, can maintain the ball control performance of the footwear, and can therefore provide significant benefits to the wearer compared to footwear articles without the material on the outsole. Thus, the material can undergo dynamic transformations, and these dynamic transformations can also create forces or conditions that dislodge accumulated dirt or otherwise reduce dirt accumulation on the article.
[0102] The total amount of water that a hydrogel can absorb depends on a variety of factors, such as its composition (e.g., its hydrophilicity), its cross-linking density, its thickness, the presence of other materials and / or the interfacial bonding with other materials, such as the third polymer material present as a backing layer in a layered film. For example, it is believed that a hydrogel comprising a polymer network with a higher hydrophilicity level and a lower cross-linking density level can increase the water absorption capacity of the hydrogel. On the other hand, the interfacial bonding between the hydrogel and the third polymer material as a backing layer in a layered film can potentially constrain the swelling of the hydrogel. Therefore, as described below, the water absorption capacity and swelling capacity of a hydrogel can be different between a hydrogel in a neat film state (a film alone in itself) and a hydrogel as present in a layered film.
[0103] The water absorption capacity and rate of water absorption of a hydrogel may also depend, at least in part, on the size and shape of its geometric structure, and are often based on the same factors. However, it has been found that to account for part size when measuring water absorption capacity, inherent steady-state material properties can be derived. Thus, conservation of mass can be used to define the ratio of the weight of absorbed water to the initial dry weight of a hydrogel over very long time scales (i.e., when the ratio no longer changes at a measurable rate).
[0104] In contrast, the rate of water absorption is instantaneous and can be defined kinetically. Given the part geometry, the three main factors for the rate of water absorption of a hydrogel present at the surface of the outsole include time, thickness, and the exposed surface area available for water absorption. Again, the weight of the water absorbed can be used as a measure of the water absorption rate, but the water flux can also be considered by normalizing the exposed surface area. For example, a thin rectangular membrane can be defined by 2×L×W, where L is the length of one side and W is the width. This value is doubled to account for the two major surfaces of the membrane, but the former factor can be eliminated when the membrane has a non-absorbent structural layer fixed to one of the major surfaces (e.g., an outsole backing plate with a third polymer material in a layered membrane).
[0105] In addition to swelling, the compliance of the polymer hydrogel material can also increase from being relatively rigid (i.e., dry state) to being gradually stretchable, compressible, and extensible (i.e., wet state). Thus, the increased compliance can allow the hydrogel to easily compress under applied pressure (e.g., during foot impact on the ground), and in some aspects, quickly expel at least a portion of its retained water (depending on the degree of compression). While not wishing to be bound by theory, it is believed that this compression compliance alone, water expulsion alone, or a combination of both can disrupt the adhesion and / or adhesion of dirt at the outsole, which prevents or otherwise reduces the accumulation of dirt on the outsole.
[0106] In addition to rapidly expelling water, in certain aspects, the compressed hydrogel is capable of rapidly reabsorbing water when compression is released (e.g., from a foot strike off the ground during normal use). Thus, during use in a wet or humid environment (e.g., a muddy or wet ground), the hydrogel can dynamically expel and repeatedly absorb water, particularly from wet surfaces, during successive foot strikes. Thus, the hydrogel can continue to prevent dirt accumulation for an extended period of time (e.g., throughout a competitive game), particularly when there is groundwater available for reabsorption.
[0107] Water Absorption Capacity - According to one aspect of the present disclosure, a polymeric hydrogel material (e.g., a hydrogel present as a sample of a portion of an outsole component prepared according to the Component Sampling Procedure, the outsole component having a hydrogel present at or defining a side or surface of the outsole from which the sample was taken) has a water absorption capacity of greater than 40% by weight in 24 hours, as characterized by the Water Absorption Capacity Test using the Component Sampling Procedure, each as described below. In some aspects, it is believed that if a particular outsole is unable to absorb greater than 40% by weight of water within a 24-hour period, either because its rate of water absorption is too slow, or because its water absorption capacity is too low (e.g., because it is thin, there may not be enough hydrogel, or the overall capacity of the hydrogel to absorb water is too low), then the outsole may not be effective in preventing or reducing soil accumulation.
[0108] For the purposes of this disclosure, the term "total water uptake capacity" is used to express the amount of water absorbed by a hydrogel as a percentage of the weight of the dry hydrogel. A procedure for measuring the total water uptake capacity may include measuring the "dry" weight of the hydrogel, immersing the hydrogel in water at ambient temperature (about 23° C.) for a predetermined amount of time, and then measuring the weight of the hydrogel again when "wet".
[0109] For the purpose of the present disclosure, the term "weight" refers to a mass value, for example, with units of grams, kilograms and the like. In addition, the description of a numerical range by an endpoint includes the endpoint and all numbers within the numerical range. For example, a concentration ranging from 40% by weight to 60% by weight includes a concentration of 40% by weight, 60% by weight, and all concentrations therebetween (e.g., 40.1%, 41%, 45%, 50%, 52.5%, 55%, 59%, etc.).
[0110] Furthermore, any range of parameters stated herein as "between [first number] and [second number]" or "between [first number] and [second number]" is intended to include the recited numbers. In other words, these ranges are meant to be similarly interpreted as ranges specified as "from [first number] to [second number]."
[0111] In additional aspects, the hydrogel (including the side or surface of the outsole component formed from the hydrogel) has a water absorption capacity of greater than 50% by weight, greater than 100% by weight, greater than 150% by weight, or greater than 200% by weight in 24 hours. In other aspects, the hydrogel has a water absorption capacity of less than 900% by weight, less than 750% by weight, less than 600% by weight, or less than 500% by weight in 24 hours.
[0112] In certain aspects, the hydrogel (including the side or surface of the outsole formed from the hydrogel) has a water absorption capacity ranging from 40% by weight to 900% by weight in 24 hours. For example, the hydrogel can have a water absorption capacity ranging from 100% by weight to 900% by weight, from 100% by weight to 750% by weight, from 100% by weight to 700% by weight, from 150% by weight to 600% by weight, from 200% by weight to 500% by weight, or from 300% by weight to 500% by weight.
[0113] These water absorption capacities can be determined by a water absorption capacity test using a component sampling procedure and can be applied to samples taken at any suitable representative location along the outsole of the shoe, wherein the membrane component forms the outermost layer of the outsole. In some cases, samples can be taken from one or more of the forefoot area, the midfoot area, and / or the heel area; from each of the forefoot area, the midfoot area, and the heel area; from within one or more traction element clusters (between traction elements) at the forefoot area, the midfoot area, and / or the heel area; from a traction element cluster; on a planar area of a traction element (for aspects where the material is present on the traction element), and combinations thereof.
[0114] As discussed below, the water absorption capacity of the hydrogel (including the side or surface of the outsole formed by the hydrogel) can be optionally measured in a simulated environment, such as using the hydrogel co-extruded with a backing substrate (e.g., a third polymer material) in a layered film. The backing substrate can be produced from any suitable thermosetting material or thermoplastic material compatible with the hydrogel, such as, but not limited to, materials conventionally used to form outsole backing plates. Therefore, as characterized by the water absorption capacity test conducted using the co-extruded or laminated film sampling procedure, suitable water absorption capacities of the hydrogel co-extruded or laminated with the backing substrate at 24 hours include those discussed above with respect to the water absorption capacity test using the component sampling procedure.
[0115] Furthermore, it has been discovered that when the hydrogel is secured to another surface, such as thermally or adhesively bonded to a substrate (e.g., a third polymeric material), the interfacial bond formed between the hydrogel and the outsole substrate can limit the extent to which the hydrogel can absorb water and / or swell. Thus, it is believed that a hydrogel, such as bonded to a substrate or co-extruded with a substrate, may potentially have a lower water absorption capacity and / or a lower swelling capacity than the same hydrogel in neat material form, including neat film form.
[0116] Therefore, the water absorption capacity and water absorption rate of the outsole component can also be characterized based on the hydrogel in pure form (e.g., a separate film that is not combined with another material). The hydrogel in pure form can have a water absorption capacity of greater than 40% by weight, greater than 100% by weight, greater than 300% by weight, or greater than 1000% by weight at 24 hours, as characterized by a water absorption capacity test using a pure film sampling procedure or a pure material sampling procedure. The hydrogel in pure form can also have a water absorption capacity of less than 900% by weight, less than 800% by weight, less than 700% by weight, less than 600% by weight, or less than 500% by weight at 24 hours.
[0117] In particular aspects, the hydrogel in pure form has a water absorption capacity in the range of from 40% by weight to 900% by weight, from 150% by weight to 700% by weight, from 200% by weight to 600% by weight, or from 300% by weight to 500% by weight in 24 hours.
[0118] Water Absorption Rate - The outsole component (including the side or surface of the outsole formed from the hydrogel) may have a water absorption rate greater than 20 grams per square meter per minute or 20 g / m 2 / √min, as characterized by a Water Absorption Rate Test using a Component Sampling Procedure. As discussed above, in some aspects, the outsole (e.g., hydrogel) can absorb water between compression cycles of foot strikes, which is believed to at least partially replenish the material between foot strikes.
[0119] Thus, in further aspects, the outsole component (including the side or surface of the outsole formed from the hydrogel) has a hydrogel strength greater than 20 g / m 2 / √min, greater than 100g / m 2 / √min, greater than 200g / m 2 / √min, greater than 400g / m 2 / √min or greater than 600g / m 2 In certain aspects, the outsole has a water absorption rate of from 1 g / m 2 / √min to 1,500g / m 2 / √min, from 20g / m 2 / √min to 1,300g / m 2 / √min, from 30g / m 2 / √min to 1,200g / m 2 / √min, from 30g / m 2 / √min to 800g / m 2 / √min, from 100g / m 2 / √min to 800g / m 2 / √min, from 100g / m 2 / √min to 600g / m 2 / √min, from 150g / m 2 / √min to 450g / m 2 / √min, from 200g / m 2 / √min to 1,000g / m 2 / √min, from 400g / m 2 / √min to 1,000g / m 2 / √min or from 600g / m 2 / √min to 900g / m 2 The water absorption rate is in the range of / √min.
[0120] Suitable water absorption rates for the hydrogel as secured to a coextruded backing substrate (e.g., a third polymeric material), as characterized by the Water Absorption Rate Test conducted using the Coextruded or Laminated Film Sampling Procedure, and suitable water absorption rates for the hydrogel as provided in neat form, as characterized by the Water Absorption Rate Test conducted using the Neat Film Sampling Procedure, each include those discussed above for the Water Absorption Rate Test conducted using the Part Sampling Procedure.
[0121] Swelling Capacity - In certain aspects, outsole components (including the sides or surfaces of the outsole formed by the hydrogel) can swell, increasing the thickness and / or volume of the hydrogel due to water absorption. Such swelling of the hydrogel can be a convenient indicator that the hydrogel is absorbing water and can help to make the hydrogel pliable. In some aspects, the outsole has a material thickness increase (or swelling thickness increase) of greater than 20% or greater than 50% at 1 hour, such as in the range of from 30% to 350%, from 50% to 400%, from 50% to 300%, from 100% to 300%, from 100% to 200%, or from 150% to 250%, as characterized by a swelling capacity test using a component sampling procedure. In other aspects, the outsole has a material thickness increase in the range of from 45% to 400%, from 100% to 350%, or from 150% to 300% at 24 hours.
[0122] In addition, the hydrogel (including the side or surface of the outsole formed by the hydrogel) can have a material volume increase (or volume swelling increase) greater than 50% at 1 hour, such as from 10% to 130%, from 30% to 100%, or from 50% to 90%. In addition, the outsole can have a material volume increase in the range of from 25% to 200%, from 50% to 150%, or from 75% to 100% at 24 hours.
[0123] For coextruded or laminated film simulations, suitable increases in material thickness and volume at 1 hour and 24 hours for a hydrogel as secured to a coextruded or laminated backing substrate as characterized by the Swell Capacity Test conducted using the Coextruded or Laminated Film Sampling Procedure include those discussed above with respect to the Swell Capacity Test conducted using the Part Sampling Procedure.
[0124] The material in pure form may have a material thickness increase in the range of from 35% to 400%, from 50% to 300%, or from 100% to 200% at 1 hour, as characterized by a swelling capacity test using a pure film sampling procedure. In some further aspects, the material in pure form may have a material thickness increase in the range of from 45% to 500%, from 100% to 400%, or from 150% to 300% at 24 hours. Accordingly, the material in pure form may have a material volume increase in the range of from 50% to 500%, from 75% to 400%, or from 100% to 300% at 1 hour.
[0125] Contact angle - in some aspects, the surface of the hydrogel forms the side or surface of the outsole, wherein the side or surface has a hydrophilic property. The hydrophilic property of the surface of the hydrogel can be characterized by determining the static sessile drop contact angle (static sessile drop contact angle) of the surface of the hydrogel. Therefore, in some aspects, the surface of the hydrogel in a dry state has a static sessile drop contact angle (or dry state contact angle) less than 105 degrees, or less than 95 degrees, less than 85 degrees, as characterized by a contact angle test. The contact angle test can be carried out on a sample obtained according to a component sampling procedure, a coextruded or laminated film sampling procedure, or a pure film sampling procedure. In some other aspects, the hydrogel in a dry state has a static sessile drop contact angle in the range of from 60 degrees to 100 degrees, from 70 degrees to 100 degrees, or from 65 degrees to 95 degrees.
[0126] In other aspects, the surface of the hydrogel in a wet state has a static sessile droplet contact angle (or wet contact angle) of less than 90 degrees, less than 80 degrees, less than 70 degrees, or less than 60 degrees. In some other aspects, the surface in a wet state has a static sessile droplet contact angle in the range of from 45 degrees to 75 degrees. In some cases, the dry static sessile droplet contact angle of the surface is at least 10 degrees, at least 15 degrees, or at least 20 degrees greater than the wet static sessile droplet contact angle of the surface, for example, from 10 degrees to 40 degrees, from 10 degrees to 30 degrees, or from 10 degrees to 20 degrees.
[0127] Coefficient of Friction - The surface of the hydrogel, including the surface of the outsole of a shoe, can also exhibit a low coefficient of friction when the hydrogel is wet. Examples of suitable coefficients of friction (or dry coefficient of friction) for hydrogels in a dry state are less than 1.5, such as in the range of from 0.3 to 1.3 or from 0.3 to 0.7, as characterized by a coefficient of friction test. The coefficient of friction test can be performed on samples obtained according to the component sampling procedure, the coextruded or laminated film sampling procedure, or the pure film sampling procedure. Examples of suitable coefficients of friction (or wet coefficient of friction) for hydrogels in a wet state are less than 0.8 or less than 0.6, such as in the range of from 0.05 to 0.6, from 0.1 to 0.6, or from 0.3 to 0.5. In addition, the hydrogel can exhibit a decrease in its coefficient of friction from its dry state to its wet state, such as a decrease in the range of from 15% to 90% or from 50% to 80%. In some cases, the dry coefficient of friction of the hydrogel is greater than the wet coefficient of friction, such as by a value of at least 0.3 or 0.5 higher, such as from 0.3 to 1.2 or from 0.5 to 1.
[0128] Storage Modulus - The compliance of a hydrogel, including the outer or ground-facing layer of an outsole comprising the hydrogel, can be characterized based on the storage modulus of the hydrogel in a dry state (when equilibrated at 0% relative humidity (RH)) and in a partially wet state (e.g., when equilibrated at 50% RH or at 90% RH), and by the decrease in its storage modulus between the dry and wet states. Specifically, the hydrogel can have a decrease in storage modulus (ΔE') from the dry state relative to the wet state. As the water concentration in the hydrogel increases, the decrease in storage modulus corresponds to an increase in compliance because less stress is required for a given strain / deformation.
[0129] In some aspects, the hydrogel exhibits a decrease in storage modulus from its dry state to its wet state (50% RH) of greater than 20%, greater than 40%, greater than 60%, greater than 75%, greater than 90%, or greater than 99%, relative to the storage modulus in the dry state and as characterized by a storage modulus test employing a neat film sampling process. In some other aspects, the dry storage modulus of the hydrogel is greater than its wet (50% RH) storage modulus by more than 25 megapascals (MPa), more than 50 MPa, more than 100 MPa, more than 300 MPa, or more than 500 MPa, such as from 25 MPa to 800 MPa, from 50 MPa to 800 MPa, from 100 MPa to 800 MPa, from 200 MPa to 800 MPa, from 400 MPa to 800 MPa, from 25 MPa to 200 MPa, from 25 MPa to 100 MPa, or from 50 MPa to 200 MPa. In addition, the dry storage modulus can be in the range of from 40 MPa to 800 MPa, from 100 MPa to 600 MPa, or from 200 MPa to 400 MPa, as characterized by a storage modulus test. Furthermore, the wet storage modulus may be in a range from 0.003 MPa to 100 MPa, from 1 MPa to 60 MPa, or from 20 MPa to 40 MPa.
[0130] In other aspects, the hydrogel exhibits a decrease in storage modulus from its dry state to its wet state (90% RH) of greater than 20%, greater than 40%, greater than 60%, greater than 75%, greater than 90%, or greater than 99%, relative to the storage modulus in the dry state and as characterized by a storage modulus test employing a neat film sampling procedure. In other aspects, the dry storage modulus of the hydrogel is greater than its wet (90% RH) storage modulus by more than 25 megapascals (MPa), more than 50 MPa, more than 100 MPa, more than 300 MPa, or more than 500 MPa, such as from 25 MPa to 800 MPa, from 50 MPa to 800 MPa, from 100 MPa to 800 MPa, from 200 MPa to 800 MPa, from 400 MPa to 800 MPa, from 25 MPa to 200 MPa, from 25 MPa to 100 MPa, or from 50 MPa to 200 MPa. In addition, the dry storage modulus can be in the range of from 40 MPa to 800 MPa, from 100 MPa to 600 MPa, or from 200 MPa to 400 MPa, as characterized by a storage modulus test. Furthermore, the wet storage modulus may be in a range from 0.003 MPa to 100 MPa, from 1 MPa to 60 MPa, or from 20 MPa to 40 MPa.
[0131] In addition to a decrease in storage modulus, the hydrogel may also exhibit a decrease in its glass transition temperature from the dry state (when equilibrated at 0% relative humidity (RH)) to the wet state (when equilibrated at 90% RH). While not wishing to be bound by theory, it is believed that water absorbed by the hydrogel plasticizes the hydrogel, which reduces its storage modulus and its glass transition temperature, making the material more compliant (e.g., compressible, expandable, and stretchable).
[0132] Glass transition temperature - In some aspects, the hydrogel can exhibit a decrease in glass transition temperature (ΔT) of more than 5°C difference, more than 6°C difference, more than 10°C difference, or more than 15°C difference from its dry (0% RH) glass transition temperature to its wet glass transition (90% RH) temperature. g ), as characterized by a glass transition temperature test using a pure film sampling process or a pure material sampling process. For example, a decrease in the glass transition temperature (ΔT g ) can range from more than 5°C difference to 40°C difference, from more than 6°C difference to 50°C difference, from more than 10°C difference to 30°C difference, from more than 30°C difference to 45°C difference, or from 15°C difference to 20°C difference. The hydrogel can also exhibit a dry glass transition temperature ranging from -40°C to -80°C or from -40°C to -60°C.
[0133] Alternatively (or additionally), a decrease in the glass transition temperature (ΔT g ) can be in the range of from 5°C difference to 40°C difference, from 10°C difference to 30°C difference, or from 15°C difference to 20°C difference. The material can also exhibit a dry glass transition temperature in the range of from -40°C to -80°C or from -40°C to -60°C.
[0134] In various aspects, the polymer hydrogel material is a thermoplastic hydrogel having a melting point of less than 150° C. For example, the onset of melting of the polymer hydrogel material can occur between 90° C. and 150° C., including between 90° C. and 135° C., and between 110° C. and 135° C. Alternatively, the polymer hydrogel material is a thermoplastic hydrogel having a melting point greater than 150° C. For example, the onset of melting of the polymer hydrogel material can occur between 150° C. and 190° C., including between 150° C. and 180° C.
[0135] In addition to effectively preventing dirt accumulation, it has also been found that the outsole of the ground-facing layer including the hydrogel is also sufficiently durable for its intended use on the outward-facing side or surface of the article. Durability is based at least in part on the properties and strength of the interface bonding of the outsole to the upper and the physical properties of the hydrogel in the outsole itself, the upper comprising a part of the finished footwear. For example, during the useful life of the finished footwear, it is desirable that the outsole may not be peeled off from the upper, and it may be generally wear-resistant or abrasion-resistant (e.g., maintaining its structural integrity without cracking or tearing). In many aspects, the useful life of the outsole (and the footwear article including the outsole) is at least 10 hours, 20 hours, 50 hours, 100 hours, 120 hours or 150 hours of use. For example, in some applications, the useful life of the outsole is in the range of from 20 hours to 120 hours. In other applications, the useful life of the outsole is in the range of from 50 hours to 100 hours of use.
[0136] The phrase "outwardly facing" as used with respect to an element or material or layer refers to the surface or side of an element that faces toward or toward the outside of the article when the element is present in the article during its intended use. If the article is footwear, the outwardly facing element may be "ground-facing", in other words, the surface or side of the element faces toward or toward the ground when the element is present in the article of footwear during normal use, that is, during normal use by a wearer in a standing position, the element is positioned toward the ground, and thus the element may contact the ground, including unpaved surfaces, when the footwear is used in a conventional manner, such as when standing, walking or running on unpaved surfaces. In other words, even if the element may not necessarily face the ground during various steps of manufacturing or transportation, if the element is expected to face the ground during normal use by the wearer, the element is understood to face the ground.
[0137] In some cases, due to the presence of elements such as traction elements, the ground-facing surface may be positioned toward the ground during normal use, but may not necessarily contact the ground. For example, on a hard ground or paved surface, the ends of the traction elements on the outsole may directly contact the ground, while the portion of the outsole located between the traction elements does not contact the ground. As described in this example, the portions of the outsole located between the traction elements are considered to be facing the ground, even though they may not directly contact the ground in all cases.
[0138] The hydrogel material in the outsole component may include a polymer hydrogel. The hydrogel material may be any material that absorbs water to provide an outsole component capable of absorbing a desired amount of water. The hydrogel material may comprise, consist of, or consist essentially of a polymer or copolymer of a polyurethane, a polyurea, a polyester, a polycarbonate, a polyetheramide, an addition polymer of an ethylenically unsaturated monomer, or any combination thereof.
[0139] As used herein, the term "polymer" refers to a molecule of a polymer unit with one or more monomeric species. It will be appreciated by those skilled in the art that the term "polymer" includes both homopolymers (i.e., polymers with the same monomeric species) and copolymers. The term "copolymer" refers to a polymer of a polymer unit with two or more monomeric species, and is understood to include terpolymers (i.e., copolymers with three monomeric species). On the other hand, "monomer" can include different functional groups or segments, but for simplicity, it is generally referred to as monomer. As used herein, "a (a)" polymer or other compounds mentioned refer to one or more molecules of a polymer or compound, and are not limited to the single molecule of a polymer or compound. In addition, the one or more molecules may be identical or may not be identical, as long as they belong to the category of the compound. Therefore, for example, "a (a)" polylaurolactam (polylaurolactam) is interpreted as including one or more polymer molecules of polylaurolactam, wherein the polymer molecules may be identical or may not be identical (e.g., different molecular weights and / or isomers).
[0140] For the purpose of the present disclosure, the term "at least one / kind" element and "one / kind or more / kind" element are used interchangeably, and can have the same meaning. Refer to these terms comprising a single element or a plurality of elements, and can also be represented by the suffix "(s)" at the end of the element. For example, "at least one polyurethane", "one or more polyurethanes" and "polyurethane (polyurethane (s))" can be used interchangeably, and are intended to have the same meaning.
[0141] Unless otherwise indicated, any functional group or compound described herein can be substituted or unsubstituted. "Substituted" group or compound, such as alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, aryl, heteroaryl, alkoxy, ester, ether or carboxylate refers to alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, aryl, heteroaryl, alkoxy, ester, ether or carboxylate group, with at least one hydrogen group replaced by non-hydrogen group (i.e. substituent). The example of non-hydrogen group (or substituent) includes but is not limited to alkyl, cycloalkyl, alkenyl, cycloalkenyl, alkynyl, ether, aryl, heteroaryl, heterocycloalkyl, hydroxyl, oxy (or oxo), alkoxy, ester, thioester, acyl, carboxyl, cyano, nitro, amino, amido, sulphur and halogen. When substituted alkyl group comprises multiple non-hydrogen groups, substituent can be attached to the same carbon atom or two or more different carbon atoms.
[0142] In one aspect, the polymer hydrogel may include, consist of, or consist essentially of a polyurethane hydrogel. The polyurethane hydrogel is prepared from one or more diisocyanates and one or more hydrophilic diols. In addition to the hydrophilic diols, the polymer may also include a hydrophobic diol. Polymerization is typically performed using approximately equal amounts of diols and diisocyanates. Examples of hydrophilic diols are polyethylene glycol or copolymers of ethylene glycol and propylene glycol. The diisocyanate may be selected from a variety of aliphatic diisocyanates or aromatic diisocyanates. The hydrophobicity of the resulting polymer is determined by the amount and type of the hydrophilic diol, the type and amount of the hydrophobic diol, and the type and amount of the diisocyanate. Examples of commercially available thermoplastic polyurethane hydrogels include, but are not limited to, thermoplastic polyurethanes sold under the trade name "TECOPHILIC", such as TG-500, TG-2000, SP-80A-150, SP-93A-100, SP-60D-60 (Lubrizol, Countryside, IL), "ESTANE" (e.g., ALR G 500; Lubrizol, Countryside, IL). Additional details about polyurethanes are provided herein.
[0143] In various aspects, the polyurethane hydrogel is a thermoplastic polyurethane hydrogel having a melting point of less than 150° C., including between 90° C. and 135° C., and between 110° C. and 135° C. Alternatively, the polyurethane hydrogel is a thermoplastic polyurethane hydrogel having a melting point greater than 150° C., including between 150° C. and 190° C., and between 150° C. and 180° C.
[0144] In one aspect, the polymer hydrogel may include, consist of or consist essentially of a polyurea hydrogel. The polyurea hydrogel is prepared from one or more diisocyanates and one or more hydrophilic diamines. In addition to the hydrophilic diamines, the polymer may also include a hydrophobic diamine. Polymerization is generally carried out using approximately equal amounts of diamines and diisocyanates. Typical hydrophilic diamines are amine-terminated polyethylene oxides and amine-terminated copolymers of polyethylene oxide / polypropylene. An example is the "JEFFAMINE" diamine sold by Huntsman (The Woodlands, TX, USA). The diisocyanate may be selected from a variety of aliphatic diisocyanates or aromatic diisocyanates. The hydrophobicity of the resulting polymer is determined by the amount and type of the hydrophilic diamine, the type and amount of the hydrophobic amine, and the type and amount of the diisocyanate. Additional details about polyurea are provided herein.
[0145] In one aspect, the polymer hydrogel may include, consist of, or consist essentially of a polyester hydrogel. The polyester hydrogel may be prepared from a dicarboxylic acid (or a dicarboxylic acid derivative) and a diol, wherein some or all of the diol is a hydrophilic diol. Examples of hydrophilic diols are polyethylene glycol or a copolymer of ethylene glycol and propylene glycol. A second hydrophobic diol may also be used to control the polarity of the final polymer. One or more diacids may be used, which may be aromatic or aliphatic. Of particular interest are block polyesters prepared from lactones of hydrophilic diols and hydroxy acids. The lactones are polymerized at each end of the hydrophilic diol to produce a triblock polymer. In addition, these triblock segments may be linked together to produce a multiblock polymer by reaction with a dicarboxylic acid. Additional details about polyureas are provided herein.
[0146] In one aspect, the polymer hydrogel may include, consist of, or consist essentially of a polycarbonate hydrogel. Polycarbonates are typically prepared by reacting a diol with phosgene or a carbonic acid diester. When part or all of the diol is a hydrophilic diol, a hydrophilic polycarbonate is produced. Examples of hydrophilic diols are hydroxyl-terminated polyethers of ethylene glycol or polyethers of ethylene glycol and propylene glycol. A second hydrophobic diol may also be included to control the polarity of the final polymer. Additional details about polycarbonates are provided herein.
[0147] In one aspect, the polymer hydrogel can include, consist of or consist essentially of a polyetheramide hydrogel. Polyetheramides are prepared from dicarboxylic acids (or dicarboxylic acid derivatives) and polyetherdiamines (polyethers terminated with amino groups at each end). Hydrophilic amine-terminated polyethers produce hydrophilic polymers that will be swollen by water. Hydrophobic diamines can be used in combination with hydrophilic diamines to control the hydrophilicity of the final polymer. In addition, the dicarboxylic acid segment type can be selected to control the polarity of the polymer and the physical properties of the polymer. Typical hydrophilic diamines are amine-terminated polyethylene oxides and amine-terminated copolymers of polyethylene oxide / polypropylene. Examples are "JEFFAMINE" diamines sold by Huntsman (The Woodlands, TX, USA). Additional details about polyetheramides are provided herein.
[0148] In one aspect, the polymer hydrogel can comprise, be composed of or be substantially composed of such a hydrogel, and the hydrogel is formed by the addition polymer of ethylenically unsaturated monomers. The addition polymer of ethylenically unsaturated monomers can be a random polymer. The polymer is prepared by free radical polymerization of one or more hydrophilic ethylenically unsaturated monomers and one or more hydrophobic ethylenically unsaturated monomers. Examples of hydrophilic monomers are acrylic acid, methacrylic acid, 2-acrylamido-2-methylpropanesulfonic acid, vinyl sulfonic acid, sodium p-styrenesulfonate, [3-(methacryloylamino)propyl] trimethylammonium chloride, methacrylate-2-hydroxyethyl, acrylamide, N, N-dimethylacrylamide, 2-vinylpyrrolidone, (meth) acrylate of polyethylene glycol and (meth) acrylate of polyethylene glycol monomethyl ether. Examples of hydrophobic monomers are (meth) acrylate of C1 to C4 alcohols, polystyrene, polystyrene methacrylate macromonomers and mono (meth) acrylate of siloxane. Water absorption and physical properties can be adjusted by selecting the monomers and the amount of each monomer type.Additional details regarding ethylenically unsaturated monomers are provided herein.
[0149] The addition polymer of ethylenically unsaturated monomers can be a comb polymer. When one of the monomers is a macromonomer (an oligomer with an ethylenically unsaturated group at one end), a comb polymer is produced. In one case, the main chain is hydrophilic and the side chain is hydrophobic. Alternatively, the comb-shaped main chain can be hydrophobic and the side chain is hydrophilic. An example is the main chain of a hydrophobic monomer such as styrene and a monomethacrylate of polyethylene glycol.
[0150] The addition polymer of ethylenically unsaturated monomers can be a block polymer. The block polymer of ethylenically unsaturated monomers can be prepared by methods such as anionic polymerization or controlled radical polymerization. Hydrogels are produced when the polymer has both hydrophilic blocks and hydrophobic blocks. The polymer can be a diblock polymer (AB) polymer, a triblock polymer (ABA) or a multiblock polymer. Triblock polymers with hydrophobic end blocks and hydrophilic center blocks are most useful for this application. Block polymers can also be prepared by other means. The partial hydrolysis of polyacrylonitrile polymers produces multiblock polymers, and the hydrophilic domains (hydrolyzed) of the multiblock polymers are separated by the hydrophobic domains (unhydrolyzed), so that the partially hydrolyzed polymers act as hydrogels. Hydrolysis converts acrylonitrile units into hydrophilic acrylamide units or acrylic acid units in a multiblock pattern.
[0151] The polymer hydrogel may comprise, consist of, or consist essentially of a hydrogel formed from a copolymer. In some aspects, the polymer hydrogel may comprise a polyurethane / polyurea copolymer, a polyurethane / polyester copolymer, or a polyester / polycarbonate copolymer.
[0152] Hydrogel material can include polymer network.In other words, hydrogel can include any suitable polymer chain, and this polymer chain provides desired functional property (such as water absorption, swelling, and more generally, prevent dirt accumulation), and desirably provides good durability for article.For example, hydrogel can be based on one or more polyurethanes, one or more polyureas, one or more polyesters, one or more polyetheramides, one or more polymers of ethylenically unsaturated monomers, one or more polyamides, one or more polyolefins and combinations thereof (such as, based on polyurethane and polyamide hydrogel).Hydrogel or cross-linked polymer network can include multiple copolymer chains, wherein at least a portion of copolymer chains each include polyurethane segment, polyamide segment or its combination.In some aspects, one or more polyurethanes, one or more polyamides, one or more polyolefins and combinations thereof include polysiloxane segment and / or ionomer segment.
[0153] In some respects, the hydrogel material comprises a hydrophilic polymer and optionally one or more additives in composition. In other respects, the hydrogel comprises a polymer network (such as a hydrophilic polymer network) and optionally one or more additives in composition. In some respects, the polymer network is preferably a plurality of cross-linked (or cross-linkable) polymer chains, wherein the polymer chain can be a combination of a homopolymer, a copolymer or a homopolymer and a copolymer. When cross-linked, the network can be physically cross-linked or covalently cross-linked, or physically cross-linked and covalently cross-linked.
[0154] For physical crosslinking, the copolymer chains can form entangled regions and / or crystalline regions through non-covalent bonding interactions, such as, for example, ionic bonds, polar bonds, and / or hydrogen bonds. In particular aspects, the crystalline regions produce physical crosslinks between the copolymer chains. As described below, the crystalline regions can include hard segments.
[0155] In some aspects, the polymer network can exhibit sol-gel reversibility, which allows it to function as a thermoplastic polymer, which can be advantageous for manufacturing and recyclability. Thus, in some aspects, the polymer network of the hydrogel includes a physically cross-linked polymer network to function as a thermoplastic material.
[0156] The hydrogel can be characterized as including both hard segments and soft segments. When the hydrogel is in a solid (non-molten) state, these hard and soft regions can exist in the polymer network as phase-separated regions. The hard segments can form part of the polymer chain backbone and can exhibit high polarity, which allows the hard segments of multiple polymer chains to aggregate together or interact with each other to form semi-crystalline regions in the polymer network. Multiple polymer chains can include one or more hard segments; and one or more soft segments covalently bonded to the hard segments, wherein the one or more soft segments are present in the copolymer chain in a ratio ranging from 20: 1 to 110: 1 by weight relative to the one or more hard segments.
[0157] "Semi-crystalline" or "crystalline" regions have an ordered molecular structure with a sharp melting point, remain solid until a given amount of heat is absorbed, and then rapidly change to a low viscosity liquid. "Pseudo-crystalline" regions have the properties of crystals but do not exhibit a true crystal diffraction pattern. For ease of reference, the term "crystalline region" is used herein to collectively refer to crystalline, semi-crystalline, and pseudo-crystalline regions of a polymer network.
[0158] In contrast, the soft segment can be a longer, more flexible, hydrophilic region of the polymer network, which allows the polymer network to expand and swell under the pressure of absorbing water. The soft segment can constitute the amorphous hydrophilic region of the hydrogel or cross-linked polymer network. The soft segment or amorphous region can also form a part of the main chain of the polymer chain together with the hard segment. In addition, one or more parts in the soft segment or amorphous region can be grafted or otherwise represent the side chain extending from the main chain at the soft segment. The soft segment or amorphous region can be covalently bonded to the hard segment or crystalline region (for example, through a carbamate bond). For example, multiple amorphous hydrophilic regions can be covalently bonded to the crystalline region of the hard segment.
[0159] As used herein, the term "hydrophilic" refers to polymers that have a strong tendency to bind or absorb water, which results in swelling and the formation of reversibly swollen gels. A "swelling gel" is a gel that absorbs an amount of water greater than at least 100 weight percent of its own weight when immersed in water.
[0160] The hydrophilic soft segments of the copolymer chain may include polyether segments, polyester segments, polycarbonate segments or combinations thereof. At least a portion of one or more hydrophilic soft segments may constitute the main chain segments of the copolymer chain. At least a portion of the hydrophilic soft segments may include one or more side chain polyether groups. The one or more hydrophilic soft segments may be present in the copolymer chain in a ratio in the range of 40:1 to 110:1 by weight relative to the one or more hard segments. The polymer network may be a cross-linked polymer network. The polymer network may be a network formed by copolymer chains. The polymer chains of the polymer network include polyurethane chain segments, polyamide chain segments or both.
[0161] According to another aspect of the present disclosure, the cross-linked polymer network of the hydrogel in the outer layer or ground-facing layer of the outsole includes a plurality of copolymer chains. At least a portion of these copolymer chains include hard segments physically cross-linked to other hard segments of the copolymer chains and soft segments covalently bonded to the hard segments, such as through carbamate groups or ester groups.
[0162] Hydrogel or cross-linked polymer network may include multiple copolymer chains. At least a portion of the copolymer chain includes a first segment and a second segment, the first segment and the other hard segments of the copolymer chain together form at least a crystalline region; the second segment is, for example, covalently bonded to a soft segment of the first segment (e.g., a segment with a polyether chain or one or more ether groups). The soft segment forms an amorphous region of a hydrogel or cross-linked polymer network. In some cases, a hydrogel or cross-linked polymer network includes multiple copolymer chains, wherein at least a portion of the copolymer chain has a hydrophilic segment.
[0163] When the polymer network of the hydrogel is crosslinked, it has been found that the crosslink density of the crosslinked polymer network can affect the structural integrity and water absorption capacity of the hydrogel. For example, if the crosslink density is too high, the resulting hydrogel may be hard and not very compliant, with relatively low water absorption and swelling capacity. On the other hand, if the crosslink density is too low, the resulting hydrogel may lose its structural integrity when saturated. Therefore, the polymer network of the hydrogel preferably has a crosslink density that is selected so that the hydrogel has a desired balance of properties, for example, it maintains its structural integrity, but is also sufficiently compliant when partially or completely saturated with water.
[0164] The hydrogel material in the lamellar film of the outsole can be formed via coextrusion or lamination with a backing plate or backing layer comprising a third polymer material. Subsequently, the second polymer material is used to complete the formation of the outsole in a molding process. The second (2nd) polymer material and / or the third (3rd) polymer material can be independently selected to include a thermosetting polymer or a thermoplastic polymer. The composition of the second polymer material and the third polymer material can be selected as substantially the same material, or can be selected as different materials selectively. When needed, the second polymer material and / or the third polymer material can include one or more natural rubbers or synthetic rubbers. Natural rubber or synthetic rubber can include but not limited to butadiene rubber, isoprene rubber or nitrile rubber. Natural rubber or synthetic rubber can be selected as new material, regrinding material or its mixture individually.
[0165] Now that aspects of hydrogel materials have been generally described, additional details are provided regarding the thermoplastic polymers referred to herein, including thermoplastic hydrogels. In various aspects, the thermoplastic polymer can include one or more polymers selected from the group consisting of polyesters, polyethers, polyamides, polyurethanes, and polyolefins, and copolymers of each or a combination thereof, such as those described herein.
[0166] In aspects, thermoplastic polymers can include polymers of the same or different types of monomers (e.g., homopolymers and copolymers, including terpolymers). In certain aspects, thermoplastic polymers can include different monomers randomly distributed in the polymer (e.g., random copolymers).
[0167] For example, a thermoplastic polymer can be a polymer that has relatively hard, repeating polymer units (hard segments) of the same chemical structure (segment) and relatively soft repeating polymer segments (soft segments). In many aspects, the polymer has repeated hard segments and soft segments, and physical crosslinking can be present in the segments or between the segments, or in the segments and between the segments. Specific examples of hard segments include isocyanate segments. Specific examples of soft segments include alkoxy groups, such as polyether segments and polyester segments. As used herein, polymer segments can be referred to as polymer segments of a specific type, such as, for example, isocyanate segments (e.g., diisocyanate segments), alkoxy polyamide segments (e.g., polyether segments, polyester segments) and similar segments. It should be understood that the chemical structure of the segments is derived from the described chemical structure. For example, an isocyanate segment is a polymer unit including an isocyanate functional group. When referring to polymer segments of a specific chemical structure, the polymer can include segments of other chemical structures up to 10mol%. For example, as used herein, a polyether segment is understood to include up to 10 mol % of a non-polyether segment.
[0168] In various aspects, the thermoplastic polymer of the outsole component, including but not limited to the thermoplastic hydrogel of the outsole component, has a melting temperature (T) from about 90° C. to about 190° C. when measured according to ASTM D3418-97 as described below. m In another aspect, the thermoplastic polymer has a melting temperature (T ) from about 93° C. to about 99° C. when measured according to ASTM D3418-97 as described below. m In yet another aspect, the thermoplastic polymer has a melting temperature (T ) from about 112° C. to about 118° C. when measured according to ASTM D3418-97 as described below. m ).
[0169] In various aspects, the thermoplastic polymer has a glass transition temperature (T ) from about -20°C to about 30°C when measured according to ASTM D3418-97 as described below. g In another aspect, the thermoplastic polymer has a glass transition temperature (T ) from about -13°C to about -7°C when measured according to ASTM D3418-97 as described below. g In yet another aspect, the thermoplastic polymer or thermoplastic hydrogel has a glass transition temperature (T ) from about 17° C. to about 23° C. when measured according to ASTM D3418-97 as described below. g ).
[0170] In various aspects, the thermoplastic polymer has a thermal conductivity of from about 10 cubic centimeters per 10 minutes (cm3) when tested according to ASTM D1238-13 at 160°C using a 2.16 kilogram (kg) weight as described below. 3 In another aspect, the thermoplastic polymer has a melt flow index of from about 22 cm3 / 10 min) to about 30 cm3 / 10 min when tested according to ASTM D1238-13 at 160°C using a 2.16 kg weight as described below. 3 / 10min to about 28cm 3 / 10min melt flow index.
[0171] In various aspects, the thermoplastic polymer has a cold Ross flex test result of about 120,000 to about 180,000 cycles without cracking or whitening when tested according to the Cold Ross Flex Test as described below on a thermoformed substrate of the thermoplastic polymer. In additional aspects, the thermoplastic polymer has a cold Ross flex test result of about 140,000 to about 160,000 cycles without cracking or whitening when tested according to the Cold Ross Flex Test as described below on a thermoformed substrate of the thermoplastic polymer.
[0172] In various aspects, the thermoplastic polymer has a modulus of from about 5 megapascals (MPa) to about 100 MPa when measured on a thermoformed substrate according to ASTM D412-98 Standard Test Method for Vulcanized Rubber and Thermoplastic Rubbers and Thermoplastic Elastomers-Tension with modifications described below. In additional aspects, the thermoplastic polymer has a modulus of from about 20 MPa to about 80 MPa when measured on a thermoformed substrate according to ASTM D412-98 Standard Test Method for Vulcanized Rubber and Thermoplastic Rubbers and Thermoplastic Elastomers-Tension with modifications described below.
[0173] In certain aspects, the thermoplastic polymer may be a thermoplastic polyurethane (also referred to as "TPU"). In aspects, the thermoplastic polyurethane may be a thermoplastic polyurethane polymer. In such aspects, the thermoplastic polyurethane polymer may include a hard segment and a soft segment. In aspects, the hard segment may include an isocyanate segment (e.g., a diisocyanate segment) or may be composed of an isocyanate segment (e.g., a diisocyanate segment). In the same or optional aspects, the soft segment may include an alkoxy segment (e.g., a polyether segment, or a polyester segment or a combination of a polyether segment and a polyester segment) or may be composed of an alkoxy segment. In specific aspects, the thermoplastic material may include an elastic thermoplastic polyurethane having a repeating hard segment and a repeating soft segment or may be substantially composed of such an elastic thermoplastic polyurethane.
[0174] Thermoplastic polyurethane
[0175] In aspects, one or more of the thermoplastic polyurethanes can be produced by polymerizing one or more isocyanates with one or more polyols to produce a polymer chain having a urethane bond (-N(CO)O-), as shown in Formula 1 below, wherein each of the isocyanates preferably contains two or more isocyanate (-NCO) groups per molecule, for example 2, 3 or 4 isocyanate groups per molecule (although monofunctional isocyanates may also optionally be included, for example as a chain terminating unit).
[0176]
[0177] In these aspects, each R1 and R2 is independently an aliphatic segment or an aromatic segment. Optionally, each R2 can be a hydrophilic segment.
[0178] In addition, the isocyanate can also be chain extended with one or more chain extenders to bridge two or more isocyanates. This can produce a polyurethane polymer chain as shown in Formula 2 below, wherein R3 includes a chain extender. Like each R1 and R3, each R3 is independently an aliphatic segment or an aromatic segment.
[0179]
[0180] Each segment R1 or the first segment in Formula 1 and Formula 2 may independently include a linear or branched C 3-30 The term "aliphatic" refers to a saturated or unsaturated organic molecule that does not include a cyclically conjugated ring system with delocalized π electrons. In contrast, the term "aromatic" refers to a cyclically conjugated ring system with delocalized π electrons, which exhibits greater stability than a hypothetical ring system with localized π electrons.
[0181] Each segment R1 may be present in an amount of 5 to 85% by weight, from 5 to 70% by weight, or from 10 to 50% by weight, based on the total weight of the reactant monomers.
[0182] In aliphatic embodiments (from aliphatic isocyanates), each segment R1 may include a linear aliphatic group, a branched aliphatic group, an alicyclic group, or a combination thereof. For example, each segment R1 may include a linear or branched C 3-20 The alkylene segment (e.g., C 4-15 Alkylene or C 6-10 alkylene), one or more C 3-8 Cycloalkylene segments (eg, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, or cyclooctyl), and combinations thereof.
[0183] Examples of suitable aliphatic diisocyanates for producing polyurethane polymer chains include hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), butylene diisocyanate (BDI), diisocyanatocyclohexylmethane (HMDI), 2,2,4-trimethylhexamethylene diisocyanate (TMDI), diisocyanatomethylcyclohexane, diisocyanatomethyltricyclodecane, norbornane diisocyanate (NDI), cyclohexane diisocyanate (CHDI), 4,4'-dicyclohexylmethane diisocyanate (H12MDI), diisocyanatododecane, lysine diisocyanate, and combinations thereof.
[0184] In one aspect, the diisocyanate segments may include aliphatic diisocyanate segments. In one aspect, most of the diisocyanate segments include aliphatic diisocyanate segments. In one aspect, at least 90% of the diisocyanate segments are aliphatic diisocyanate segments. In one aspect, the diisocyanate segments are substantially composed of aliphatic diisocyanate segments. In one aspect, the aliphatic diisocyanate segments are generally (e.g., about 50% or more, about 60% or more, about 70% or more, about 80% or more, about 90% or more) straight-chain aliphatic diisocyanate segments. In one aspect, at least 80% of the aliphatic diisocyanate segments are aliphatic diisocyanate segments without side chains. In one aspect, the aliphatic diisocyanate segments include C2-C10 straight-chain aliphatic diisocyanate segments.
[0185] In aromatic embodiments (from aromatic isocyanates), each segment R1 may contain one or more aromatic groups, such as phenyl, naphthyl, tetrahydronaphthyl, phenanthrenyl, biphenylenyl, indanyl, indenyl, anthracenyl, and fluorenyl. Unless otherwise indicated, aromatic groups may be unsubstituted aromatic groups or substituted aromatic groups, and may also include heteroaromatic groups. "Heteroaromatic" refers to monocyclic or polycyclic (e.g., fused bicyclic and fused tricyclic) aromatic ring systems, wherein one to four ring atoms are selected from oxygen, nitrogen, or sulfur, and the remaining ring atoms are carbon, and wherein the ring system is connected to the rest of the molecule via any ring atoms. Examples of suitable heteroaryl groups include pyridyl, pyrazinyl, pyrimidinyl, pyrrolyl, pyrazolyl, imidazolyl, thiazolyl, tetrazolyl, oxazolyl, isoxazolyl, thiadiazolyl, oxadiazolyl, furanyl, quinolyl, isoquinolyl, benzoxazolyl, benzimidazolyl and benzothiazolyl.
[0186] Examples of suitable aromatic diisocyanates for producing polyurethane polymer chains include toluene diisocyanate (TDI), TDI adducts with trimethylolpropane (TMP), methylene diphenyl diisocyanate (MDI), xylene diisocyanate (XDI), tetramethyl xylene diisocyanate (TMXDI), hydrogenated xylene diisocyanate (HXDI), naphthalene-1,5-diisocyanate (NDI), 1,5-tetrahydronaphthalene diisocyanate, p-phenylene diisocyanate (PPDI), 3,3'-dimethyldiphenyl-4,4'-diisocyanate (DDDI), 4,4'-dibenzyl diisocyanate (DBDI), 4-chloro-1,3-phenylene diisocyanate, and combinations thereof. In some aspects, the polymer chain is substantially free of aromatic groups.
[0187] In a particular aspect, the polyurethane polymer chain is composed of HMDI, TDI, MDI, H 12 For example, the low processing temperature polymer composition of the present disclosure may include one or more polyurethane polymer chains produced from diisocyanates including HMDI, TDI, MDI, H 12 Aliphatic compounds and combinations thereof.
[0188] In certain aspects, according to the present disclosure, crosslinked polyurethane chains (e.g., partially crosslinked polyurethane polymers that retain thermoplastic properties) or crosslinked polyurethane chains can be used. It is possible to use multifunctional isocyanates to produce crosslinked or crosslinkable polyurethane polymer chains. Examples of suitable triisocyanates for producing polyurethane polymer chains include TDI, HDI and IPDI adducts with trimethylolpropane (TMP), uretdione (i.e., diisocyanates), polymeric MDI and combinations thereof.
[0189] The chain segment R3 in Formula 2 may include linear or branched C2-C 10The chain segments may be, for example, aliphatic, aromatic or polyether. Examples of suitable chain extender polyols for producing polyurethane polymer chains include ethylene glycol, lower oligomers of ethylene glycol (e.g., diethylene glycol, triethylene glycol and tetraethylene glycol), 1,2-propylene glycol, 1,3-propylene glycol, lower oligomers of propylene glycol (e.g., dipropylene glycol, tripropylene glycol and tetrapropylene glycol), 1,4-butanediol, 2,3-butanediol, 1,6-hexanediol, 1,8-octanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, 2-ethyl-1,6-hexanediol, 1-methyl-1,3-propanediol, 2-methyl-1,3-propanediol, dihydroxyalkylated aromatic compounds (e.g., bis(2-hydroxyethyl)ether of hydroquinone and resorcinol, xylene-a,a-diol, bis(2-hydroxyethyl)ether of xylene-a,a-diol and combinations thereof.
[0190] The segment R2 in Formula 1 and Formula 2 may include a polyether group, a polyester group, a polycarbonate group, an aliphatic group, or an aromatic group. Based on the total weight of the reactant monomers, each segment R2 may be present in an amount of 5% to 85% by weight, from 5% to 70% by weight, or from 10% to 50% by weight.
[0191] In some examples, at least one R2 segment of the thermoplastic polyurethane includes a polyether segment (i.e., a segment having one or more ether groups). Suitable polyethers include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), polytetrahydrofuran (PTHF), polytetramethylene oxide (PTMO), and combinations thereof. As used herein, the term "alkyl" refers to a straight chain and branched saturated hydrocarbon group containing one to thirty carbon atoms, such as one to twenty carbon atoms or one to ten carbon atoms. The term C n It means that the alkyl group has "n" carbon atoms. For example, C4 alkyl refers to an alkyl group with 4 carbon atoms. 1-7 Alkyl refers to an alkyl group having a carbon number covering the entire range (i.e., 1-7 carbon atoms) and all subgroups (e.g., 1-6, 2-7, 1-5, 3-6, 1, 2, 3, 4, 5, 6 and 7 carbon atoms). The non-limiting examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl (2-methylpropyl), tert-butyl (1,1-dimethylethyl), 3,3-dimethylpentyl and 2-ethylhexyl. Unless otherwise indicated, alkyl groups can be unsubstituted alkyl groups or substituted alkyl groups.
[0192] In some examples of thermoplastic polyurethane, the at least one R2 segment includes a polyester segment. The polyester segment can be derived from the polyesterification of one or more dihydroxy alcohols (e.g., ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, 1,3-butylene glycol, 2-methylpentanediol, 1,5-diethylene glycol, 1,5-pentanediol, 1,5-hexanediol, 1,2-dodecanediol, cyclohexanedimethanol, and combinations thereof) and one or more dicarboxylic acids (e.g., adipic acid, succinic acid, sebacic acid, suberic acid, methyl adipic acid, glutaric acid, pimelic acid, azelaic acid, thiodipropionic acid, and citraconic acid, and combinations thereof). The polyester can also be derived from a polycarbonate prepolymer, such as poly(hexamethylene carbonate) glycol, poly(propylene carbonate) glycol, poly(tetramethylene carbonate) glycol, and poly(nonanemethylene carbonate) glycol. Suitable polyesters can include, for example, polyethylene adipate (PEA), poly(1,4-butylene adipate), poly(tetramethylene adipate), poly(hexamethylene adipate), polycaprolactone, polyhexamethylene carbonate, poly(propylene carbonate), poly(tetramethylene carbonate), poly(nonamethylene carbonate), and combinations thereof.
[0193] In a variety of thermoplastic polyurethanes, at least one R2 segment includes a polycarbonate segment. The polycarbonate segment can be derived from the reaction of one or more dihydroxy alcohols (e.g., ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, 1,3-butylene glycol, 2-methylpentanediol, 1,5-diethylene glycol, 1,5-pentanediol, 1,5-hexanediol, 1,2-dodecanediol, cyclohexanedimethanol, and combinations thereof) with ethylene carbonate.
[0194] In various examples, aliphatic groups are linear and may include, for example, C 1-20 Alkylene chain or C 1-20 Alkenylene chains (e.g., methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, decylene, undecylene, dodecylene, tridecylene, vinylene, propenylene, butenylene, pentenylene, hexenylene, heptenylene, octenylene, nonenylene, decenylene, undecenylene, dodecenylene, tridecenylene). The term "alkylene" refers to a divalent hydrocarbon. The term Cn means that the alkylene group has "n" carbon atoms. For example, Cn 1-6 Alkylene refers to an alkylene group having, for example, 1, 2, 3, 4, 5, or 6 carbon atoms. The term "alkenylene" refers to a divalent hydrocarbon having at least one double bond.
[0195] In many aspects, aliphatic groups and aromatic groups can be replaced by one or more relatively hydrophilic and / or charged side groups. In some aspects, hydrophilic side groups include one or more (for example, 2,3,4,5,6,7,8,9,10 or more) hydroxyl groups. In many aspects, hydrophilic side groups include one or more (for example, 2,3,4,5,6,7,8,9,10 or more) amino groups. In some cases, hydrophilic side groups include one or more (for example, 2,3,4,5,6,7,8,9,10 or more) carboxylate groups. For example, aliphatic groups can include one or more polyacrylic acid groups. In some cases, hydrophilic side groups include one or more (for example, 2,3,4,5,6,7,8,9,10 or more) sulfonate groups. In some cases, the hydrophilic side groups include one or more (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10 or more) phosphate groups. In some instances, the hydrophilic side groups include one or more ammonium groups (e.g., tertiary ammonium and / or quaternary ammonium). In other instances, the hydrophilic side groups include one or more zwitterionic groups (e.g., betaines, such as poly (carboxybetaine (pCB)) and ammonium phosphonate groups such as phosphatidylcholine groups).
[0196] In some aspects, the R2 segment can include a charged group capable of binding a counterion to ionically crosslink the thermoplastic polymer and form an ionomer. In these aspects, for example, R2 is an aliphatic or aromatic group having an amino side group, a carboxylate side group, a sulfonate side group, a phosphate side group, an ammonium side group, or a zwitterionic side group, or a combination thereof.
[0197] In many cases, when hydrophilic side groups are present, the "hydrophilic" side groups are at least one polyether group, such as two polyether groups. In other cases, the hydrophilic side groups are at least one polyester. In many cases, the hydrophilic side groups are polylactone groups (e.g., polyvinylpyrrolidone). Each carbon atom in the hydrophilic side groups can be optionally replaced by, for example, C 1-6 Alkyl group substitution. In some of these aspects, the aliphatic group and the aromatic group can be a grafted polymer group, wherein the pendant group is a homopolymer group (eg, a polyether group, a polyester group, a polyvinylpyrrolidone group).
[0198] In some aspects, the hydrophilic side groups are polyether groups (eg, polyethylene oxide groups, polyethylene glycol groups), polyvinyl pyrrolidone groups, polyacrylic acid groups, or combinations thereof.
[0199] The hydrophilic side group can be bonded to the aliphatic group or aromatic group through a linker. The linker can be any bifunctional small molecule (e.g., C 1-20). For example, the linking group may include a diisocyanate group as previously described herein that forms a urethane bond when attached to a hydrophilic side group and to an aliphatic or aromatic group. In some aspects, the linking group may be 4,4'-diphenylmethane diisocyanate (MDI), as shown below.
[0200]
[0201] In some exemplary aspects, the hydrophilic pendant group is a polyethylene oxide group and the linking group is MDI, as shown below.
[0202]
[0203] In some respects, the hydrophilic side group is functionalized so that it can be optionally attached to aliphatic groups or aromatic groups by a linking group. In many aspects, for example, when the hydrophilic side group includes an olefin group, the olefin group can be subjected to Michael addition (Michael addition) with the difunctional molecule (that is, the molecule with the second reactive group such as hydroxyl group or amino group) containing sulfydryl, to produce a hydrophilic group, the hydrophilic group can use the second reactive group and the polymer backbone, optionally reacted by a linking group. For example, when the hydrophilic side group is a polyvinylpyrrolidone group, it can react with the sulfhydryl group on mercaptoethanol, to produce hydroxy-functionalized polyvinylpyrrolidone, as shown below.
[0204]
[0205] In some aspects disclosed herein, at least one R2 segment includes a polytetramethylene oxide group. In other exemplary aspects, at least one R2 segment may include an aliphatic polyol group functionalized with a polyethylene oxide group or a polyvinyl pyrrolidone group, such as the polyol described in European Patent No. 2462908, which is incorporated by reference accordingly. For example, the R2 segment may be derived from a polyol (e.g., pentaerythritol or 2,2,3-trihydroxypropanol) with a methoxypolyethylene glycol derived from MDI (to obtain a compound as shown in Formula 6 or Formula 7) or with a polyvinyl pyrrolidone derived from MDI (to obtain a compound as shown in Formula 8 or Formula 9) The reaction product, the methoxypolyethylene glycol derived from MDI and the polyvinyl pyrrolidone derived from MDI have been previously reacted with mercaptoethanol, as shown below.
[0206]
[0207]
[0208] In various aspects, at least one R2 is a polysiloxane. In these cases, R2 can be derived from a siloxane monomer of Formula 10, such as the siloxane monomers disclosed in U.S. Pat. No. 5,969,076, which is hereby incorporated by reference:
[0209]
[0210] wherein: a is 1 to 10 or greater (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10); each R4 is independently hydrogen, C 1-18 Alkyl, C 2-18 alkenyl, aryl or polyether; and each R5 is independently C 1-10 Alkylene, polyether or polyurethane.
[0211] In some aspects, each R4 is independently hydrogen, C 1-10 Alkyl, C 2-10 Alkenyl, C 1-6 Aryl, polyethylene, polypropylene or polybutene groups. For example, each R4 can be independently selected from the group consisting of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, vinyl, propenyl, phenyl and polyethylene groups.
[0212] In various aspects, each R5 independently comprises C 1-10 In some embodiments, each R5 is a polyurethane group. In some embodiments, each R5 is a alkylene group (e.g., a methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, or decylene group). In other embodiments, each R5 is a polyether group (e.g., a polyethylene, polypropylene, or polybutylene group). In many embodiments, each R5 is a polyurethane group.
[0213] Optionally, in some aspects, the polyurethane may include an at least partially cross-linked polymer network including polymer chains that are derivatives of the polyurethane. In such cases, it is understood that the cross-linking level is such that the polyurethane retains thermoplastic properties (i.e., the cross-linked thermoplastic polyurethane may soften or melt and resolidify under the processing conditions described herein). As shown in Formulas 11 and 12 below, the cross-linked polymer network may be produced by polymerizing one or more isocyanates with one or more polyamino compounds, polysulfhydryl compounds, or a combination thereof:
[0214]
[0215] wherein the variables are as described above. In addition, the isocyanate can also be chain extended with one or more polyamino or polythiol chain extenders to bridge two or more isocyanates, such as described above for the polyurethane of Formula 2.
[0216] As described herein, thermoplastic polyurethane can be physically cross-linked by non-polar interactions or polar interactions between, for example, urethane or carbamate groups (hard segments) on polymers. In these aspects, component R1 in formula 1 and components R1 and R3 in formula 2 form a polymer portion commonly referred to as a "hard segment", and component R2 forms a polymer portion commonly referred to as a "soft segment". In these aspects, the soft segment can be covalently bonded to the hard segment. In some instances, the thermoplastic polyurethane with physically cross-linked hard segments and soft segments can be a hydrophilic thermoplastic polyurethane (i.e., a thermoplastic polyurethane containing a hydrophilic group as disclosed herein).
[0217] Thermoplastic polyamide
[0218] In many aspects, the thermoplastic polymer may include a thermoplastic polyamide. The thermoplastic polyamide may be a polyamide homopolymer having a repeating polyamide segment of the same chemical structure. Alternatively, the polyamide may include a number of polyamide segments (e.g., polyamide 6 segments, polyamide 11 segments, polyamide 12 segments, polyamide 66 segments, etc.) having different polyamide chemical structures. The polyamide segments having different chemical structures may be randomly arranged, or may be arranged as repeating blocks.
[0219] In aspect, the thermoplastic polymer can be a block copolyamide. For example, the block copolyamide can have repeated hard segments and repeated soft segments. The hard segments can include polyamide segments, and the soft segments can include non-polyamide segments. The thermoplastic polymer can be an elastic thermoplastic copolyamide, which includes or consists of a block copolyamide with repeated hard segments and repeated soft segments. In a block copolymer including a block copolymer with repeated hard segments and soft segments, physical crosslinking can be present within a segment or between segments, or both within a segment and between segments.
[0220] Thermoplastic polyamide can be a copolyamide (i.e., a copolymer comprising a polyamide segment and a non-polyamide segment). The polyamide segment of the copolyamide can include or be composed of: a polyamide 6 segment, a polyamide 11 segment, a polyamide 12 segment, a polyamide 66 segment, or any combination thereof. The polyamide segment of the copolyamide can be arranged randomly, or can be arranged as a repeating segment. In a specific example, the polyamide segment can include or be composed of: a polyamide 6 segment, or a polyamide 12 segment, or both a polyamide 6 segment and a polyamide 12 segment. In the example where the polyamide segment of the copolyamide includes a polyamide 6 segment and a polyamide 12 segment, the segment can be arranged randomly. The non-polyamide segment of the copolyamide can include or be composed of: a polyether segment, a polyester segment, or both a polyether segment and a polyester segment. The copolyamide can be a block copolyamide, or can be a random copolyamide. Thermoplastic copolyamides may be formed by polycondensation of a polyamide oligomer or prepolymer with a second oligomer prepolymer to form a copolyamide (ie, a copolymer comprising polyamide segments). Optionally, the second prepolymer may be a hydrophilic prepolymer.
[0221] In some aspects, the thermoplastic polyamide itself or the polyamide segments of the thermoplastic copolyamide can be derived from the condensation of a polyamide prepolymer such as a lactam, an amino acid and / or a diamino compound with a dicarboxylic acid or an activated form thereof. The resulting polyamide segments contain amide bonds (-(CO)NH-). The term "amino acid" refers to a molecule having at least one amino group and at least one carboxyl group. Each polyamide segment of the thermoplastic polyamide can be the same or different.
[0222] In some aspects, the polyamide segment of the thermoplastic polyamide or thermoplastic copolyamide is derived from the polycondensation of lactam and / or amino acid and comprises an amide segment having the structure shown in Formula 13 below, wherein R6 is a polyamide segment derived from lactam or amino acid.
[0223]
[0224] In some aspects, R6 is derived from lactam. In some cases, R6 is derived from C 3-20 lactam, or C 4-15 Lactam or C 6-12 Lactam. For example, R6 can be derived from caprolactam or laurolactam. In some cases, R6 is derived from one or more amino acids. In many cases, R6 is derived from C 4-25 Amino acids, or C 5-20 Amino acids or C 8-15 Amino acids. For example, R6 may be derived from 12-aminolauric acid or 11-aminoundecanoic acid.
[0225] Optionally, to increase the relative hydrophilicity of the thermoplastic copolyamide, Formula 13 may include polyamide-polyether block copolymer segments, as shown below:
[0226]
[0227] wherein m is 3-20, and n is 1-8. In some exemplary aspects, m is 4-15 or 6-12 (e.g., 6, 7, 8, 9, 10, 11 or 12), and n is 1, 2 or 3. For example, m can be 11 or 12, and n can be 1 or 3. In various aspects, the polyamide segment of the thermoplastic polyamide or thermoplastic copolyamide is derived from the condensation of a diamino compound with a dicarboxylic acid or an activated form thereof, and comprises an amide segment having a structure shown in Formula 15 below, wherein R7 is a polyamide segment derived from a diamino compound, and R8 is a segment derived from a dicarboxylic acid compound:
[0228]
[0229] In some aspects, R7 is derived from a diamino compound comprising 4-15 Carbon atom, or C 5-10 Carbon atom, or C 6-9 In some aspects, the diamino compound comprises an aromatic group, such as phenyl, naphthyl, xylyl and tolyl. Suitable diamino compounds from which R7 can be derived include, but are not limited to, hexamethylenediamine (HMD), tetramethylenediamine, trimethylhexamethylenediamine (TMD), meta-xylyldiamine (MXD) and 1,5-pentamine diamine. In various aspects, R8 is derived from a dicarboxylic acid or an activated form thereof, including a dicarboxylic acid having C 4-15 Carbon atom, or C 5-12 Carbon atom, or C 6-10 In some cases, R8 may be derived from a dicarboxylic acid or an activated form thereof including aromatic groups, such as phenyl, naphthyl, xylyl and tolyl groups. Suitable carboxylic acids or activated forms thereof that R8 may be derived from include, but are not limited to, adipic acid, sebacic acid, terephthalic acid and isophthalic acid. In some aspects, the polymer chain is substantially free of aromatic groups.
[0230] In some aspects, each polyamide segment of the thermoplastic polyamide (including thermoplastic copolyamide) is independently derived from a polyamide prepolymer selected from the group consisting of 12-aminolauric acid, caprolactam, hexamethylenediamine, and adipic acid.
[0231] In some aspects, the thermoplastic polyamide comprises or consists of a thermoplastic poly(ether-block-amide). The thermoplastic poly(ether-block-amide) can be formed by the polycondensation of a carboxylic acid terminated polyamide prepolymer and a hydroxyl terminated polyether prepolymer to form a thermoplastic poly(ether-block-amide), as shown in Formula 16:
[0232]
[0233] In various aspects, the disclosed poly(ether block amide) polymers are prepared by polycondensation of polyamide blocks containing reactive ends with polyether blocks containing reactive ends. Examples include, but are not limited to: 1) polyamide blocks containing diamine chain ends with polyoxyalkylene blocks containing carboxylic acid chain ends; 2) polyamide blocks containing dicarboxylic acid chain ends with polyoxyalkylene blocks containing diamine chain ends, the polyoxyalkylene blocks containing diamine chain ends being obtained by cyanoethylation and hydrogenation of aliphatic dihydroxylated α-ω polyoxyalkylenes known as polyether diols; 3) polyamide blocks containing dicarboxylic acid chain ends with polyether diols, in which case the product obtained is a polyetheresteramide. The polyamide blocks of the thermoplastic poly(ether-block-amide) can be derived from lactams, amino acids and / or diamino compounds with dicarboxylic acids, as previously described. The polyether block may be derived from one or more polyethers selected from the group consisting of polyethylene oxide (PEO), polypropylene oxide (PPO), polytetrahydrofuran (PTHF), polytetramethylene oxide (PTMO), and combinations thereof.
[0234] The disclosed poly(ether block amide) polymers include those comprising polyamide blocks containing dicarboxylic acid chain ends derived from the condensation of an α,ω-aminocarboxylic acid, a lactam, or a dicarboxylic acid with a diamine in the presence of a chain-limited dicarboxylic acid. In this type of poly(ether block amide) polymer, an α,ω-aminocarboxylic acid such as aminoundecanoic acid may be used; a lactam such as caprolactam or lauroyl lactam may be used; a dicarboxylic acid such as adipic acid, sebacic acid, or dodecanedioic acid may be used; and a diamine such as hexamethylenediamine may be used; or various combinations of any of the foregoing. In various aspects, the copolymer comprises a polyamide block comprising polyamide 12 or polyamide 6.
[0235] The disclosed poly(ether block amide) polymers include those containing polyamide blocks, and are of low quality, i.e., they have an Mn of from 400 to 1000, and the polymers containing polyamide blocks are derived from the condensation of one or more α,ω-aminocarboxylic acids and / or one or more lactams containing from 6 to 12 carbon atoms in the presence of dicarboxylic acids containing from 4 to 12 carbon atoms. In this type of poly(ether block amide) polymers, α,ω-aminocarboxylic acids such as aminoundecanoic acid or aminododecanoic acid can be used; dicarboxylic acids such as adipic acid, sebacic acid, isophthalic acid, succinic acid, 1,4-cyclohexyldicarboxylic acid, terephthalic acid, sodium or lithium salts of sulfoisophthalic acid, dimerized fatty acids (these dimerized fatty acids have a dimer content of at least 98% and are preferably hydrogenated) and dodecanedioic acid HOOC-(CH2) can be used. 10 -COOH; and lactams such as caprolactam and lauroyl lactam may be used; or various combinations of any of the foregoing. In various aspects, the copolymer comprises a polyamide block obtained by condensation of lauroyl lactam in the presence of adipic acid or dodecanedioic acid and having a number average molecular weight of 750, with a melting point of 127°C-130°C. In other aspects, the various components of the polyamide block and their proportions may be selected so as to obtain a melting point of less than 150°C, and advantageously a melting point between 90°C and 135°C.
[0236] The disclosed poly(ether block amide) polymers include those polymers comprising polyamide blocks derived from the condensation of at least one α,ω-aminocarboxylic acid (or lactam), at least one diamine, and at least one dicarboxylic acid. In copolymers of this type, the α,ω-aminocarboxylic acids, lactams and dicarboxylic acids may be selected from those described above as well as diamines such as aliphatic diamines containing from 6 to 12 atoms and may be acyclic and / or saturated cyclic, for example but not limited to hexamethylenediamine, piperazine, 1-aminoethylpiperazine, diaminopropylpiperazine, tetramethylenediamine, octamethylenediamine, decamethylenediamine, dodecamethylenediamine, 1,5-diaminohexane, 2,2,4-trimethyl-1,6-diaminohexane, diamine polyols, isophorone diamine (IPD), methylpentamethylenediamine (MPDM), bis(aminocyclohexyl)methane (BACM) and bis(3-methyl-4-aminocyclohexyl)methane (BMACM) may be used.
[0237] In various aspects, the components of the polyamide blocks and their proportions can be selected so as to obtain a melting point of less than 150° C. and advantageously between 90° C. and 135° C. In further aspects, the various components of the polyamide blocks and their proportions can be selected so as to obtain a melting point of less than 150° C. and advantageously between 90° C. and 135° C.
[0238] In one aspect, the number average molar mass of the polyamide block can be from about 300 grams per mole (g / mol) to about 15,000 g / mol, from about 500 g / mol to about 10,000 g / mol, from about 500 g / mol to about 6,000 g / mol, from about 500 g / mol to 5,000 g / mol, and from about 600 g / mol to about 5,000 g / mol. In other aspects, the number average molecular weight of the polyether block can be in the range of from about 100 g / mol to about 6,000 g / mol, from about 400 g / mol to 3000 g / mol, and from about 200 g / mol to about 3,000 g / mol. In still other aspects, the polyether (PE) content (x) of the poly(ether block amide) polymer can be from about 0.05 to about 0.8 (i.e., from about 5 mole percent to about 80 mole percent). In yet other aspects, the polyether block can be present at from about 10 weight percent to about 50 weight percent, from about 20 weight percent to about 40 weight percent, and from about 30 weight percent to about 40 weight percent. The polyamide block can be present at from about 50 weight percent to about 90 weight percent, from about 60 weight percent to about 80 weight percent, and from about 70 weight percent to about 90 weight percent.
[0239] In one aspect, the polyether blocks may contain units other than ethylene oxide units, such as, for example, propylene oxide or polytetrahydrofuran (which results in a polybutylene glycol sequence). It is also possible to use PEG blocks, i.e. blocks composed of ethylene oxide units; PPG blocks, i.e. blocks composed of propylene oxide units; and PTMG blocks, i.e. blocks composed of tetramethylene glycol units, also known as polytetrahydrofuran, simultaneously. PPG blocks or PTMG blocks are advantageously used. The amount of polyether blocks in these copolymers containing polyamide blocks and polyether blocks may be from about 10 weight percent to about 50 weight percent and from about 35 weight percent to about 50 weight percent of the copolymer.
[0240] The copolymer comprising polyamide blocks and polyether blocks can be prepared by any means for attaching polyamide blocks and polyether blocks. In practice, basically two processes are used, one is a two-step process and the other is a one-step process.
[0241] In the two-step process, polyamide blocks with dicarboxylic acid chain ends are first prepared, and then, in a second step, these polyamide blocks are connected to polyether blocks. The polyamide blocks with dicarboxylic acid chain ends derive from the condensation of polyamide precursors in the presence of a chain terminator dicarboxylic acid. If the polyamide precursor is only a lactam or an α,ω-aminocarboxylic acid, the dicarboxylic acid is added. If the precursor already contains a dicarboxylic acid, this is used in excess relative to the stoichiometry of the diamine. The reaction generally takes place between 180° C. and about 300° C., preferably 200° C. to 290° C., and the pressure in the reactor can be set between 5 bar and 30 bar and maintained for about 2 to 3 hours. The pressure in the reactor is slowly reduced to atmospheric pressure, and then excess water is distilled off, for example for one or two hours.
[0242] After the polyamide with carboxylic acid end groups has been prepared, the polyether, polyol and catalyst are then added. The total amount of the polyether can be divided into one or more portions and added in one or more portions, as can the catalyst. In one aspect, the polyether is first added, and the reaction of the OH end groups of the polyether and the polyol with the COOH end groups of the polyamide is started, wherein ester bonds are formed and water is eliminated. Water is removed from the reaction mixture as much as possible by distillation, and then the catalyst is introduced to complete the connection of the polyamide block to the polyether block. This second step is carried out under stirring, preferably under a vacuum of at least 50 mbar (5000 Pascal), at a temperature that makes the reactants and the obtained copolymer in a molten state. For example, the temperature can be between 100°C and 400°C, and generally between 200°C and 250°C. The reaction is monitored by measuring the torque applied by the polymer melt on the stirrer or by measuring the electrical power consumed by the stirrer. The end of the reaction is determined by the value of the torque or the target power. The catalyst is defined as any product that promotes the connection of the polyamide block to the polyether block by esterification. Advantageously, the catalyst is a derivative of a metal (M) selected from the group formed by titanium, zirconium and hafnium. In one aspect, the derivative can be prepared from a tetraalkoxide conforming to the general formula M(OR)4, wherein M represents titanium, zirconium or hafnium, and R, which may be the same or different, represents a linear or branched alkyl group having from 1 to 24 carbon atoms.
[0243] In other aspects, the catalyst can comprise the salt of metal (M), particularly the salt of (M) and organic acid, and the complex salt of the oxide of (M) and / or the hydroxide of (M) and organic acid. In still other aspects, the organic acid can be formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, sad, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, cyclohexanecarboxylic acid, phenylacetic acid, benzoic acid, salicylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, toxilic acid, fumaric acid, phthalic acid and crotonic acid. Acetic acid and propionic acid are particularly preferred. In some aspects, M is zirconium, and such salt is referred to as zirconyl salt (zirconyl salt), for example, the commercially available product sold with the name zirconyl acetate (zirconyl acetate).
[0244] In one aspect, the weight ratio of the catalyst varies from about 0.01 percent to about 5 percent of the weight of the mixture of dicarboxylic acid polyamide and polyether diol and polyol. In another aspect, the weight ratio of the catalyst varies from about 0.05 percent to about 2 percent of the weight of the mixture of dicarboxylic acid polyamide and polyether diol and polyol.
[0245] In the one-step process, the polyamide precursor, the chain terminator and the polyether are blended together; what is then obtained is a polymer having essentially polyether blocks and polyamide blocks of very variable lengths, but also having various reactants that have reacted randomly, which are randomly distributed along the polymer chain. They are the same reactants and the same catalyst as in the two-step process described above. If the polyamide precursor is only a lactam, it is advantageous to add a small amount of water. The copolymer has essentially the same polyether blocks and the same polyamide blocks, but also a small portion of various reactants that have reacted randomly, which are randomly distributed along the polymer chain. As in the first step of the two-step process described above, the reactor is closed and heated under stirring. The pressure is determined to be between 5 bar and 30 bar. When the pressure no longer changes, the reactor is placed under reduced pressure, while still maintaining vigorous stirring of the molten reactants. The reaction is monitored as previously in the case of the two-step process.
[0246] The appropriate ratio of polyamide blocks to polyether blocks can be found in a single poly(ether block amide), or a blend of two or more poly(ether block amides) of different composition can be used with the appropriate average composition. In one aspect, it may be useful to blend a block copolymer having a higher level of polyamide groups with a block copolymer having a higher level of polyether blocks to produce a blend having an average level of polyether blocks of about 20 to 40 weight percent and preferably about 30 to 35 weight percent of the total blend of poly(amide-block-ether) copolymers. In further aspects, the copolymer comprises a blend of two different poly(ether-block-amides), the blend comprising at least one block copolymer having a polyether block level of less than about 35 weight percent and a second poly(ether-block-amide) having at least about 45 weight percent polyether blocks.
[0247] Exemplary commercially available copolymers include, but are not limited to, copolymers available under the following trade names or other similar materials produced by various other suppliers: VESTAMID (Evonik Industries); PLATAMID (Arkema), for example, product code H2694; PEBAX (Arkema), for example, product codes "PEBAX MH1657" and "PEBAX MV1074"; PEBAXRNEW (Arkema); GRILAMID (EMS-Chemie AG).
[0248] In some respects, thermoplastic polyamide is physically crosslinked by the nonpolar or polar interaction between the polyamide groups of, for example, polymers. In the example where thermoplastic polyamide is a thermoplastic copolyamide, thermoplastic copolyamide can be physically crosslinked by the interaction between polyamide groups and optionally by the interaction between copolymer groups. When thermoplastic copolyamide is physically crosslinked by the interaction between polyamide groups, the polyamide segment can form the part of the polymer referred to as "hard segment", and the copolymer segment can form the part of the polymer referred to as "soft segment". For example, when thermoplastic copolyamide is a thermoplastic poly(ether-block-amide), the polyamide segment forms the hard segment part of the polymer, and the polyether segment can form the soft segment part of the polymer. Therefore, in some instances, thermoplastic polymers can include a physically crosslinked polymer network having one or more polymer chains with amide bonds.
[0249] In some aspects, the polyamide segment of the thermoplastic copolyamide includes polyamide-11 or polyamide-12, and the polyether segment is a segment selected from the group consisting of polyethylene oxide segments, polypropylene oxide segments, and polytetramethylene oxide segments, and combinations thereof.
[0250] Optionally, the thermoplastic polyamide may be partially covalently crosslinked, as previously described herein. In such cases, it is understood that the degree of crosslinking present in the thermoplastic polyamide is such that, when it is thermally processed in the form of a yarn or fiber to form an article of footwear of the present disclosure, the partially covalently crosslinked thermoplastic polyamide retains sufficient thermoplastic characteristics such that the partially covalently crosslinked thermoplastic polyamide softens or melts and resolidifies during processing.
[0251] Thermoplastic polyester
[0252] In aspect, thermoplastic polymer can include thermoplastic polyester.Thermoplastic polyester can be formed by the reaction of one or more carboxylic acid or its ester-forming derivative with one or more divalent or polyvalent aliphatic alcohol, alicyclic alcohol, aromatic alcohol or araliphatic alcohol or bisphenol.Thermoplastic polyester can be a polyester homopolymer with repeated polyester segments of the same chemical structure.Alternatively, polyester can include many polyester segments (such as polyglycolic acid segments, polylactic acid segments, polycaprolactone segments, polyhydroxyalkanoate segments, polyhydroxybutyrate segments, etc.) with different polyester chemical structures.Polyester segments with different chemical structures can be randomly arranged, or can be arranged as repeated blocks.
[0253] Exemplary carboxylic acids that can be used to prepare thermoplastic polyesters include, but are not limited to, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, nonane dicarboxylic acid, decanedicarboxylic acid, undecanedicarboxylic acid, terephthalic acid, isophthalic acid, alkyl-substituted or halogenated terephthalic acid, alkyl-substituted or halogenated isophthalic acid, nitro-terephthalic acid, 4,4′-diphenyl ether dicarboxylic acid, 4,4′-diphenyl sulfide dicarboxylic acid, 4,4′-diphenyl sulfone-dicarboxylic acid, 4,4′-diphenyl alkylene dicarboxylic acids, naphthalene-2,6-dicarboxylic acid, cyclohexane-1,4-dicarboxylic acid, and cyclohexane-1,3-dicarboxylic acid. Exemplary diols or phenols suitable for preparing thermoplastic polyesters include, but are not limited to, ethylene glycol, diethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,2-propylene glycol, 2,2-dimethyl-1,3-propanediol, 2,2,4-trimethylhexanediol, p-xylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and bisphenol A.
[0254] In some aspects, the thermoplastic polyester is polybutylene terephthalate (PBT), polytrimethylene terephthalate, polyhexamethylene terephthalate, poly-1,4-dimethylcyclohexane terephthalate, polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyarylate (PAR), polybutylene naphthalate (PBN), liquid crystal polyester, or a blend or mixture of two or more thereof.
[0255] The thermoplastic polyester can be a copolyester (i.e., a copolymer comprising a polyester segment and a non-polyester segment). The copolyester can be an aliphatic copolyester (i.e., a copolyester in which both the polyester segment and the non-polyester segment are aliphatic). Alternatively, the copolyester can contain an aromatic segment. The polyester segments of the copolyester can include or consist of a polyglycolic acid segment, a polylactic acid segment, a polycaprolactone segment, a polyhydroxyalkanoate segment, a polyhydroxybutyrate segment, or any combination thereof. The polyester segments of the copolyester can be randomly arranged, or can be arranged as repeating blocks.
[0256] For example, the thermoplastic polyester can be a block copolyester having repeating blocks (hard segments) of polymer units of the same chemical structure (segments) that are relatively hard and repeating blocks (soft segments) of polymer segments that are relatively soft. In a block copolyester including a block copolyester having repeating hard segments and soft segments, physical crosslinks can exist within a block or between blocks, or both within a block and between blocks. In a specific example, the thermoplastic material can include or consist essentially of an elastic thermoplastic copolyester having repeating block hard segments and repeating block soft segments.
[0257] The non-polyester segment of the copolyester may include or consist of the following: a polyether segment, a polyamide segment, or both a polyether segment and a polyamide segment. The copolyester may be a block copolyester, or may be a random copolyester. The thermoplastic copolyester may be formed by the polycondensation of a polyester oligomer or prepolymer with a second oligomer prepolymer to form a block copolyester. Optionally, the second prepolymer may be a hydrophilic prepolymer. For example, the copolyester may be formed by the polycondensation of terephthalic acid or naphthalene dicarboxylic acid with ethylene glycol, 1,4-butanediol or 1,3-propylene glycol. Examples of copolyesters include polyethylene adipate, polybutylene succinate, poly (3-hydroxybutyrate-co-3-hydroxyvalerate), polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate and combinations thereof. In a particular example, the copolyamide can include or consist of polyethylene terephthalate.
[0258] In some aspects, the thermoplastic polyester is a block copolymer comprising segments of one or more of the following: polybutylene terephthalate (PBT), polytrimethylene terephthalate, polyhexamethylene terephthalate, poly-1,4-dimethylcyclohexane terephthalate, polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyarylate (PAR), polybutylene naphthalate (PBN), and liquid crystal polyesters. For example, a suitable thermoplastic polyester as a block copolymer may be a PET / PEI copolymer, a polybutylene terephthalate / tetraethylene glycol copolymer, a polyoxyalkylene imide diacid / polybutylene terephthalate copolymer, or a blend or mixture of any of the foregoing copolymers.
[0259] In some aspects, the thermoplastic polyester is a biodegradable resin, such as a copolyester in which a poly(α-hydroxy acid) such as polyglycolic acid or polylactic acid is included as a major repeating unit.
[0260] The disclosed thermoplastic polyesters can be prepared by a variety of polycondensation methods known to the skilled artisan, such as solvent polymerization processes or melt polymerization processes.
[0261] Thermoplastic Polyolefin
[0262] In some aspects, thermoplastic polymers can include thermoplastic polyolefins or be substantially composed of thermoplastic polyolefins. Useful exemplary thermoplastic polyolefins can include but are not limited to polyethylene, polypropylene and thermoplastic olefin elastomers (e.g., ethylene and metallocene-catalyzed block copolymers with 4 to about 8 carbon atoms of alpha-olefins). In other aspects, thermoplastic polyolefins are polymers including polyethylene, ethylene-alpha-olefin copolymers, ethylene-propylene rubber (EPDM), polybutene, polyisobutylene, poly-4-methylpent-1-ene, polyisoprene, polybutadiene, ethylene-methacrylic acid copolymers and olefin elastomers, such as dynamically cross-linked polymers (dynamically cross-linked polymer) obtained from polypropylene (PP) and ethylene-propylene rubber (EPDM), and aforesaid blends or mixtures. Other exemplary thermoplastic polyolefins that can be used in disclosed compositions, yarns and fibers are polymers of cycloolefins such as cyclopentene or norbornene.
[0263] It should be understood that the polyethylene that may be optionally cross-linked includes various polyethylenes, including but not limited to low density polyethylene (LDPE), linear low density polyethylene (LLDPE), (VLDPE) and (ULDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), high density and high molecular weight polyethylene (HDPE-HMW), high density and ultra high molecular weight polyethylene (HDPE-UHMW), and blends or mixtures of any of the foregoing polyethylenes. The polyethylene may also be a polyethylene copolymer derived from monomers of monoolefins and dienes copolymerized with vinyl, acrylic acid, methacrylic acid, ethyl acrylate, vinyl alcohol and / or vinyl acetate. The polyolefin copolymer containing vinyl acetate derived units may be a high vinyl acetate content copolymer, such as a composition greater than about 50 weight percent vinyl acetate derived.
[0264] In some aspects, thermoplastic polyolefin as disclosed herein can be formed via free radical polymerization, cationic polymerization and / or anionic polymerization by methods well known to those skilled in the art (for example, using peroxide initiators, heat and / or light). In other aspects, the disclosed thermoplastic polyolefin can be prepared by free radical polymerization at high pressure and high temperature. Alternatively, thermoplastic polyolefin can be prepared by catalytic polymerization using a catalyst, and the catalyst generally contains one or more metals from the metal of IVb family, Vb family, VIb family or VIII family. Catalyst generally has one or more than one ligand complexed with IVb family, Vb family, VIb family or VIII family metal, generally oxide, halide, alcoholate, ester, ether, amine, alkyl, alkenyl and / or aromatic groups that can be para-coordinated or ortho-coordinated. In many aspects, the metal complex can be in free form or fixed on a substrate, generally fixed on activated magnesium chloride, titanium chloride (III), aluminum oxide or silicon oxide. It should be understood that the metal catalyst can be soluble or insoluble in the polymerization medium. The catalyst can be used alone for the polymerization, or an additional activator can be used, typically a metal alkyl of Group Ia, Group IIa and / or Group IIIa, a metal hydride, a metal alkyl halide, a metal alkyl oxide or a metal alkyloxane. The activator can conveniently be modified with additional ester groups, ether groups, amine groups or silyl ether groups.
[0265] Suitable thermoplastic polyolefins can be prepared by polymerization of monomers of monoolefins and diolefins as described herein. Exemplary monomers that can be used to prepare the disclosed thermoplastic polyolefins include, but are not limited to, ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 2-methyl-1-propylene, 3-methyl-1-pentene, 4-methyl-1-pentene, 5-methyl-1-hexene, and mixtures thereof.
[0266] Suitable ethylene-α-olefin copolymers may be obtained by copolymerization of ethylene with an α-olefin having a carbon number of 3 to 12, such as propylene, butene-1, hexene-1, octene-1,4-methyl-1-pentene, and the like.
[0267] A suitable dynamically crosslinked polymer can be obtained by crosslinking a rubber component as a soft segment while physically dispersing a hard segment such as PP and a soft segment such as EPDM by using a kneading machine such as a Banbury mixer and a twin-screw extruder.
[0268] In some aspects, the thermoplastic polyolefin can be a mixture of thermoplastic polyolefins, such as a mixture of two or more polyolefins disclosed herein above. For example, a suitable thermoplastic polyolefin mixture can be a mixture of polypropylene and polyisobutylene, a mixture of polypropylene and polyethylene (e.g., PP / HDPE, PP / LDPE), or a mixture of different types of polyethylene (e.g., LDPE / HDPE).
[0269] In some aspects, the thermoplastic polyolefin can be a copolymer of a suitable monoolefin monomer or a copolymer of a suitable monoolefin monomer and a vinyl monomer. Exemplary thermoplastic polyolefin copolymers include, but are not limited to, ethylene / propylene copolymers, linear low density polyethylene (LLDPE), and mixtures thereof with low density polyethylene (LDPE), propylene / but-1-ene copolymers, propylene / isobutylene copolymers, ethylene / but-1-ene copolymers, ethylene / hexene copolymers, ethylene / methylpentene copolymers, ethylene / heptene copolymers, ethylene / octene copolymers, propylene / butadiene copolymers, isobutylene / isoprene copolymers, ethylene / alkyl acrylate copolymers, ethylene / alkyl methacrylate copolymers, ethylene / vinyl acetate copolymers, and mixtures thereof with monooxygen ethylene-propylene copolymers, LDPE / ethylene-vinyl acetate copolymers (EVA), LDPE / ethylene-acrylic acid copolymers (EAA), LLDPE / EVA, LLDPE / EAA and alternating or random polyalkylene / carbon monoxide copolymers and mixtures thereof with other polymers, such as polyamides.
[0270] In some aspects, the thermoplastic polyolefin can be a polypropylene homopolymer, a polypropylene copolymer, a polypropylene random copolymer, a polypropylene block copolymer, a polyethylene homopolymer, a polyethylene random copolymer, a polyethylene block copolymer, a low density polyethylene (LDPE), a linear low density polyethylene (LLDPE), a medium density polyethylene, a high density polyethylene (HDPE), or a blend or mixture of one or more of the foregoing polymers.
[0271] In some aspects, the polyolefin is polypropylene. As used herein, the term "polypropylene" is intended to encompass any polymer composition comprising propylene monomers, either alone or in a mixture or copolymer with other randomly selected and oriented polyolefins, dienes or other monomers (e.g., ethylene, butene and the like). This term also encompasses any different configurations and arrangements of the component monomers (e.g., atactic, syndiotactic, isotactic and the like). Therefore, the term as applied to fibers is intended to encompass actual long lines, bands, sutures and the like of stretched polymers. Polypropylene can have any standard melt flow (by testing); however, standard fiber-grade polypropylene resins have a melt flow index range between about 1 and 1000.
[0272] In some respects, polyolefin is polyethylene. As used herein, the term "polyethylene" is intended to encompass any polymer composition comprising ethylene monomers, which are either alone or with other randomly selected and oriented polyolefins, dienes or other monomers (e.g., propylene, butene and the like) or a mixture or copolymer. This term also encompasses any different configurations and arrangements (e.g., atactic, syndiotactic, isotactic and similar) of the constituent monomers. Therefore, the term as applied to fibers is intended to encompass actual long lines, bands, sutures and the like of stretched polymers. Polyethylene can have any standard melt flow (by testing); however, standard fiber-grade polyethylene resins have a melt flow index range between about 1 and 1000.
[0273] Commercially available thermoplastic polyamide hydrogels suitable for use in the present invention include those sold under the following trade names: "PEBAX" (e.g., "PEBAX MH1657" and "PEBAX MV1074" from Arkema, Inc., Clear Lake, TX) and "SERENE" coatings (Sumedics, Eden Prairie, MN). Suitable commercially available polyolefin materials include, but are not limited to, the "POLYOX" product line and styrene block copolymers from Dow Chemical, Midland MI. Commercially available styrenic copolymers include, but are not limited to, TPE-s (e.g., styrene-butadiene-styrene (SBS) block copolymers, such as "SOFPRENE" and styrene-ethylene-butylene-styrene (SEBS) block copolymers, such as "LAPRENE" from SO.F.TER. GROUP, Lebanon, TN); thermoplastic copolyester elastomers (e.g., thermoplastic elastomer vulcanizates (TPE-v or TPV)), such as "FORPRENE" from SO.F.TER. GROUP), "TERMOTON-V" from Termopol, Istanbul Turkey, and TPE block copolymers, such as "SANTOPRENE" (ExxonMobil, Irving, TX).
[0274] According to some aspects, the second polymeric material and / or the third polymeric material may further comprise, consist of, or consist essentially of one or more processing aids. These processing aids may be independently selected from the group including, but not limited to, curing agents, initiators, plasticizers, mold release agents, lubricants, antioxidants, flame retardants, dyes, pigments, reinforcing fillers and non-reinforcing fillers, fiber reinforcements, and light stabilizers.
[0275] Alternatively, the outsole of the finished article of footwear in the present disclosure can be characterized based on its structure. For example, the outsole can be described based on, without limitation, the thickness or size of the hydrogel located on the outward-facing surface of the outsole surface, the manner in which the layered film is arranged in the finished article of footwear, the number of traction friction elements present, or whether the outsole is attached to a shoe upper comprising a single piece or multiple pieces. According to one aspect, the outsole has an outward-facing surface that is at least partially composed of a hydrogel material. Based on the total surface area of the outward-facing surface of the outsole surface, the outward-facing surface of the outsole can include from at least 10%, at least 25%, at least 50%, at least 70%, at least 80%, or between about 5% and about 95% of the hydrogel. The outsole can also include one or more traction friction elements located on its outward-facing surface.
[0276] According to another aspect of the present disclosure, the outsole exhibits a "dry" thickness in the range of about 0.1 millimeters (mm) to about 9.0 mm. Alternatively, the dry thickness of the outsole is about 0.2 mm to about 5.0 mm; alternatively, about 0.2 mm to about 2.0 mm. The hydration and swelling of the hydrogel can be observed by the increase in the thickness of the outsole from the dry thickness, through a series of intermediate thicknesses when the hydrogels are hydrated, and finally reaching a saturated thickness, which is the average thickness of the outsole when the hydrogel is fully saturated with water. For example, the saturated thickness for a fully saturated outsole can be greater than 150%, greater than 200%, greater than 250%, greater than 300%, greater than 350%, greater than 400%, or greater than 500% of the dry thickness of the outsole.
[0277] The dry and wet states of the hydrogel in the outsole can allow the footwear to dynamically adapt durability to account for dry and wet surface motion. For example, when used on dry ground, the hydrogel can be substantially dry, in which case the hydrogel is relatively hard and more wear-resistant. Alternatively, when used on wet ground or when wet material is present on dry ground, the hydrogel can quickly absorb water to reach a hydrated or fully saturated state, in which state the hydrogel material can be in a swollen and / or relatively compliant state. However, as compared to dry ground, wet ground faces less wear and tear on the swollen and compliant hydrogel. Therefore, the outsole can be used under a variety of conditions as needed. Nevertheless, the footwear is particularly useful for use in wet environments, such as muddy surfaces, grass surfaces, and similar wet environments.
[0278] The outsole may be directly fixed or otherwise operably fixed to the upper using any suitable mechanism or method. As used herein, the term "operably fixed to", for example, for an outsole that is operably fixed to an upper, refers collectively to directly connected, indirectly connected, integrally formed, and combinations thereof. For example, for an outsole that is operably fixed to an upper, the outsole may be directly connected to the upper (e.g., directly adhered to the upper or glued with a bonding agent, primer, or adhesive), may be integrally formed with the upper (e.g., as a single component), and combinations thereof.
[0279] The upper of a footwear has a body that may be made of materials known in the art for making articles of footwear and is configured to receive a user's foot. The upper of a shoe consists of all the components of the shoe above the outsole. The different components of the upper may include an inner toe box; a heel counter; and an Achilles notch, to name a few. These components are attached by stitching, or more likely molded to become a single unit to which the outsole is attached.
[0280] The upper or parts of the upper generally include a soft body made of one or more lightweight materials. The materials used in the upper provide stability, comfort and a secure fit. For example, the upper may be made of or include one or more parts made of one or more of the following: natural or synthetic leather, a thermosetting polymer, a thermoplastic polymer or a mixture thereof. When desired, the upper may be made using one of these components as a fabric or textile formed therefrom.
[0281] Textiles may include: knitted, braided, woven or non-woven textiles made entirely or partially of natural fibers; knitted, braided, woven or non-woven textiles made entirely or partially of synthetic polymers, films of synthetic polymers, etc.; and combinations thereof. Textiles may include one or more natural or synthetic fibers or yarns. Synthetic yarns may include, consist of, or consist essentially of thermoplastic polyurethane (TPU), polyamides (e.g., "nylon", etc.), polyesters (e.g., polyethylene terephthalate or PET), polyolefins, or mixtures thereof.
[0282] The upper and components of the upper can be manufactured according to conventional techniques (e.g., molding, extrusion, thermoforming, stitching, knitting, etc.). Figure 3B and Figure 3D 8 is shown as a generic design, but upper 85 may alternatively have any desired aesthetic design, functional design, brand designator, or the like.
[0283] Still refer to Figure 3D The upper 85 may also include laces, flaps, straps, or other securing or foot engaging structures 90 for securely holding the shoe 80 on the wearer's foot. A tongue member, bootie, or other similar type of structure may be provided at or near the instep area to enhance comfort and / or adjust the pressure or feel applied to the wearer's foot by any foot engaging structure 108.
[0284] When desired, at least a portion of the upper 85 of the article of footwear, and in some aspects substantially the entire upper, can be formed by a knitted component. Thus, the textile can be a knitted textile, of which a circular knitted textile is a specific example. The knitted component can additionally or alternatively form another element of the article of footwear 80, such as, for example, an insole.
[0285] The knitted component may have a first side (e.g., facing the cavity of the footwear article) forming the inner surface of the upper and a second side forming the outer surface of the upper. The upper including the knitted component may substantially surround the void so as to substantially surround the foot of the person when the footwear article is used. The first side and the second side of the knitted component may present different characteristics (e.g., the first side may provide wear resistance and comfort, while the second side may be relatively rigid and provide water resistance). The knitted component may be formed as an integrated one-piece element in a knitting process such as a weft knitting process (e.g., with a knitting flat machine or a circular knitting machine), a warp knitting process, or any other suitable knitting process. That is, the knitting process may substantially form the knitted structure of the knitted component without requiring a significant post-knitting process or step. Optionally, two or more parts of the knitted component may be formed separately and then attached. In some aspects, the knitted component may be formed after the knitting process to form and maintain the desired shape of the upper (e.g., by using a foot-shaped shoe last). The forming process may include attaching the knitted component to another object (e.g., a strobel) by sewing, by using an adhesive, or by another suitable attachment process, and / or attaching one portion of the knitted component to another portion of the knitted component at a seam.
[0286] The use of knitted components to form the upper can provide advantageous features for the upper, including but not limited to a certain degree of elasticity (e.g., expressed in Young's modulus), breathability, flexibility, strength, hygroscopicity, weight, and wear resistance. These characteristics can be achieved by selecting a specific single-layer or multi-layer knitted structure (e.g., a ribbed knit structure, a single-sided plain knit structure, or a double-sided plain knit structure), by changing the size and tension of the knitted structure, by using one or more yarns formed by a specific material (e.g., a polyester material, a monofilament material, or an elastic material such as spandex), by selecting a yarn of a specific size (e.g., denier), or a combination thereof. The knitted component can also provide desired aesthetic features by including yarns with different colors or other visual features arranged in a specific pattern. The yarn and / or knitted structure of the knitted component can be varied at different locations so that the knitted component has two or more parts with different properties (e.g., a portion forming the throat area of the upper can be relatively elastic, while another portion can be relatively inelastic). In some aspects, a knitted component can include one or more materials having properties that change in response to a stimulus (e.g., temperature, humidity, electric current, magnetic field, or light). For example, a knitted component can include yarns formed from polymer materials (e.g., polyurethanes, polyamides, polyolefins, and nylons) that transition from a solid state to a softened state or liquid state when subjected to a particular temperature at or above its melting point, and then transition back to a solid state when cooled. The polymer material can provide the ability to heat and then cool a portion of the knitted component, thereby forming a region of bonded or continuous material that exhibits certain advantageous properties, including, for example, relatively high stiffness, strength, and water resistance.
[0287] In some aspects, a knitted component may include one or more yarns or strands that are at least partially embedded or otherwise inserted into the knitted structure of the knitted component during or after the knitting process, which are referred to herein as "tension threads." The tension threads may be substantially inelastic so as to have a substantially fixed length. The tension threads may extend through multiple horizontal rows of the knitted component or through a passage within the knitted component and may limit the stretching of the knitted component in at least one direction. For example, the tension threads may extend generally from a bite line of the upper to a throat area of the upper to limit the stretching of the upper in a lateral direction. The tension threads may form one or more lace apertures for receiving laces and / or may extend around at least a portion of the lace apertures formed in the knitted structure of the knitted component.
[0288] When necessary, the footwear article may also include the use of an adhesive, primer, or combination thereof between the outsole and the upper attached thereto. The adhesive or primer may include, but is not limited to, epoxy, polyurethane, acrylic, cyanoacrylate, silicone, or a combination thereof.
[0289] According to various aspects, at least a portion of the outer surface of the outsole can include a pattern or texture. When desired, the pattern can represent a tread pattern. In some aspects, the outer surface of the outsole includes one or more traction friction elements (e.g., Figure 2A-2B and Figures 3A-3D ), wherein the portion of the traction friction element that contacts the ground is substantially free of hydrogel material. In aspects, the traction friction element comprises a material that is harder than the hydrogel material. In some aspects, the one or more traction friction elements may have a conical or rectangular shape, as further described below. The traction friction element may enhance the traction friction between the outsole and the ground. The traction friction element may also provide support or flexibility to the outsole and / or provide an aesthetic design or appearance to the footwear article.
[0290] According to many aspects, the traction friction element may include but is not limited to projections of various shapes, such as anti-skids, spikes, sole spikes or similar elements, which are configured to enhance the traction friction between the outsole and the ground for the wearer during sharp turns, steering, stopping, accelerating and backward movement. According to these aspects, the traction friction element can be arranged along the bottom surface of the outsole with any necessary or desired pattern. For example, the traction friction element can be distributed in groups or clusters along the outsole (for example, clusters of 2-8 traction friction elements). In some aspects, the traction friction element can be symmetrically or asymmetrically arranged between the medial side and the lateral side of the footwear article along the outsole. In some aspects, one or more of the traction friction elements can be arranged between the medial side and the lateral side along the center line of the outsole.
[0291] According to some aspects, the traction friction element can be made of one or more materials that are different from the hydrogel, the second polymer material, the third polymer material or the fourth polymer material constituting the outsole. In some aspects, one or more of the traction friction elements may include the same material as the second polymer material, the third polymer material or the fourth polymer material. In some aspects, one or more of the traction friction elements include the second polymer material, the third polymer material or the fourth polymer material, and can be formed integrally with the outsole during the molding step described in the method for manufacturing the outsole as defined herein. In other aspects, at least one of the traction friction elements may be substantially free of the second polymer material, the third polymer material or the fourth polymer material. In some aspects, one or more traction friction elements are made of a harder material than the second polymer material, the third polymer material or the fourth polymer material.
[0292] For example, in some aspects, the traction friction element may include one or more of the following polymer materials: thermoplastic elastomers; thermosetting polymers; elastic polymers; silicone polymers; natural rubber and synthetic rubber; composite materials including polymers reinforced with carbon fiber and / or glass; natural leather; metals such as aluminum, steel, and the like; and combinations thereof. In some aspects, the traction friction element is formed integrally with the outsole (e.g., molded together), and the traction friction element may include the same material as the component (e.g., a thermoplastic material or a thermosetting material). In some aspects, the traction friction element is provided separately (i.e., not molded with the outsole) and may be otherwise operably coupled to the outsole. For example, the outsole may include certain accessories or receptacles or receiving holes to which the traction friction element may be coupled. In these aspects, the traction friction element may include any suitable material (e.g., metal and polymer material) that can be fixed in a receiving hole of the outsole as a snap fit, screw-on, or similar manner.
[0293] In some aspects, the traction friction element can independently have any necessary or desired size (e.g., shape and size). The example of the shape of the traction friction element includes rectangle, hexagon, cylinder, cone, circle, square, triangle, trapezoid, rhombus, oval and other regular or irregular shapes (e.g., curve, C-shaped, etc.). In some aspects, the traction friction element can have the same or different height, width and / or thickness. The suitable size of the traction friction element and the other example of the arrangement along the outsole of the shoe are included in the size provided in soccer (soccer) / international soccer (globalfootball) footwear, which are from Nike, Inc. of Beaverton, OR, and the trade names are "TIEMPO", "HYPERVENOM", "MAGISTA" and "MERCURIAL" are commercially available.
[0294] In a number of aspects, the traction friction element can be incorporated into the outsole by any necessary or desired mechanism so that the traction friction element extends from the bottom surface of the outsole. In some aspects, the traction friction element can be formed integrally with the outsole by a molding process. In some aspects, the outsole can be configured to receive a removable traction friction element, such as a screw-in or snap-in traction friction element. In these aspects, the outsole can include a receiving hole (e.g., a threaded or snap-fit hole) or an accessory, and the traction friction element can be screwed into or snapped into the receiving hole or accessory, or otherwise connected to the receiving hole or accessory to fix the traction friction element to the outsole.
[0295] In other aspects, the first portion of the traction friction element can be formed integrally with the outsole, and the second portion of the traction friction element can be fixed by screwing in, snapping in, or other similar mechanisms. If desired, the traction friction element can also be configured as a short spike for use with an artificial ground (AG) shoe. In some aspects, the receiving hole or accessory can be raised or protruded from the general plane of the outer surface of the outsole. In some aspects, the receiving hole can be flush with the outer surface. In some aspects, the outsole can include a combination of these features and elements.
[0296] According to various aspects, one or more traction friction elements have a length (the size of the outward-facing surface of the outsole) greater than the thickness of the outsole in a hydrated or saturated state. The materials present in the outsole and their corresponding dry and saturated thicknesses can be selected to ensure that the traction friction elements continue to provide traction friction that engages the ground during the use of the footwear, even when the hydrogel is in a fully swollen state. For example, the outsole can be characterized by a "clearance", which is the difference between the length of one or more traction friction elements and the thickness of the outsole (in its dry state, hydrated state or saturated state). In some aspects, the average clearance for the saturated state of the outsole is ideally at least 8 millimeters (mm). In some aspects, the average clearance of the outsole in its saturated state can be at least 9mm, at least 10mm or more.
[0297] Because the outsole is the outermost sole of the shoe, it is directly exposed to wear and tear. In some aspects, the different parts of the outsole can be configured to have different thicknesses, and can show different degrees of flexibility. The outsole can include materials selected to provide necessary or desired performance, such as waterproof degree, durability and / or sufficiently high coefficient of friction to prevent sliding. In some cases, two or more materials of different densities can be incorporated into the outsole to provide a wear-resistant outer surface. In some aspects, the wear-resistant outsole can be combined with a softer, more flexible midsole for greater comfort. For example, the midsole can include a foam material formed as a sheet stock (sheetstock) by injection molding or compression molding. In some aspects, the foam material can be, but not limited to, polyurethane (PU), ethylene vinyl acetate (EVA), rubber or a combination thereof.
[0298] In some aspects, the article of footwear or shoe may also include a platform on which the foot rests and which separates the upper from the wearer's foot. The platform is typically a separate, removable plate called an insole (not shown) made of cellulose or other material, such as a thermoplastic elastomer or a thermosetting elastomer, that provides a cushion between the ground and the wearer's foot. The insole may be treated with an additive to inhibit bacterial growth. When desired, the insole may be combined with the upper, such as by being sewn into the upper.
[0299] Refer again Figure 3B and Figure 3DIn some aspects, outsole 65 of shoe 80 can be joined with or attached to upper 85, such as by being directly adhered to upper 85. In some aspects, at least a portion of the outsole can be attached to upper 85 using other means conventionally known or used in the construction of footwear 80, such as by using a cement or adhesive, by a mechanical connector, and by stitching or sewing, to name a few.
[0300] According to another aspect of the present disclosure, the use of an outsole comprising a hydrogel in composition on an outer or ground-facing surface is described. Such use includes incorporating the outsole as an outward-facing surface into a finished article of footwear to prevent or reduce dirt accumulation on the outsole and article. In some aspects, the outsole component or article retains at least 5% or less dirt by weight; alternatively, at least 10% or less dirt, compared to a conventional component or article that is similar except that the outward-facing surface of the conventional component or article is substantially free of hydrogel.
[0301] The following specific examples are given to illustrate the sampling procedures and test methods for measuring the performance exhibited by the outsole of the shoe formed according to the teachings of the present disclosure. These specific examples should not be interpreted in a manner that limits the scope of the present disclosure. According to the present disclosure, those skilled in the art will appreciate that many changes can be made to the specific embodiments disclosed herein and still obtain the same or similar results without departing from or exceeding the spirit or scope of the present disclosure. Those skilled in the art will also appreciate that any performance reported herein represents a conventionally measured performance and can be obtained by a variety of different methods. The method described herein represents a such method, and other methods can be used without exceeding the scope of the present disclosure.
[0302] Example 1 - Sampling Procedure
[0303] The predetermined sampling procedure may be a component sampling procedure when the component is present as an outsole component or as an outsole that forms part of an article of footwear; a coextruded or laminated film sampling procedure when the component is part of a layered film; a pure film sampling procedure when the component is simply a film of a hydrogel; or a pure material sampling procedure when the component is a material available in a form other than a film. Each of these sampling procedures is described in more detail below.
[0304] (A)—Parts Sampling Procedure
[0305] This procedure can be used to obtain a sample of the hydrogel when the hydrogel is used as a first layer in an outsole component or as an outer layer in an outsole of an article of footwear (e.g., bonded to a backing material such as a second polymer material and / or a third polymer material). When formed into an outsole component or cut from an article of footwear using a blade, an outsole sample is obtained that includes the hydrogel in a non-wet state (e.g., at about 25° C. and about 20% relative humidity). The process is performed by separating the outsole component from the associated upper (if present) and removing any material from the top surface of the article (e.g., corresponding to the top surface) that can absorb water and potentially distort the water absorption measurement of the hydrogel. For example, the top surface of the article can be peeled, buffed, scraped, or otherwise cleaned to remove any upper adhesives, yarns, fibers, foams, and the like that can potentially absorb water themselves.
[0306] The resulting outsole component sample includes the hydrogel and any article substrate bonded to the hydrogel, and maintains the interfacial bonding between the hydrogel and the associated backing material of the finished product. Thus, any test using the component sampling procedure can simulate how the hydrogel will perform as part of an article of footwear. In addition, this type of sample is also useful in cases where the interfacial bonding between the hydrogel and the backing material is less well defined, such as where the outsole hydrogel is highly diffused into the backing material of the finished product (e.g., with a concentration gradient).
[0307] In this procedure, samples are collected at locations along the outsole component that provide the component with a substantially constant thickness (within plus or minus 10% of the average thickness), such as in the forefoot region, midfoot region, or heel region of the article, and have a thickness of approximately 4.0 square centimeters (cm 2 ) surface area. In the hydrogel, there is no 2 Any part of the outsole component of the shoe surface area and / or for a 4.0cm 2 Where the partial thickness of the surface area is not substantially constant, a sample size having a smaller cross-sectional surface area may be collected and the measurements of the specific area adjusted accordingly.
[0308] (B)—Sampling Procedure for Coextruded or Laminated Films
[0309] This procedure can be used to obtain a hydrogel sample of the present disclosure when the hydrogel is coextruded with a backing substrate (e.g., a third polymer material) or laminated to a backing substrate to form all or part of a layered film, such as a film component used in a shoe outsole of the present disclosure. The backing substrate represents a thermoplastic material that is compatible with the components of the hydrogel.
[0310] In some cases, samples collected from coextruded films are suitable alternatives to samples collected directly from the outsole or article of footwear. In addition, such samples are also useful in cases where the interface between the hydrogel and the backing substrate is not well defined, such as where the material is highly diffused into a component of the backing substrate (e.g., with a concentration gradient).
[0311] In this case, the hydrogel is coextruded or laminated with the backing substrate into a web or sheet having a substantially constant thickness for the material (within plus or minus 10% of the average material thickness), and cooled to solidify the resulting web or sheet. A hydrogel sample fixed to the backing substrate is then cut from the resulting web or sheet, having a 4 cm 2 The sample size surface area is such that the material of the resulting sample remains fixed to the backing substrate.
[0312] (C)—Pure Film Sampling Procedure
[0313] This procedure can be used to obtain hydrogel samples of the present disclosure when the hydrogel is isolated in a pure form (i.e., without any bound substrate in a layered film). In this case, the hydrogel is extruded into a web or sheet having a substantially constant material thickness for the hydrogel (within plus or minus 10% of the average material thickness), and cooled to solidify the resulting web or sheet. A 4 cm thick sheet is then cut from the resulting web or sheet. 2 The surface area of the hydrogel sample.
[0314] Alternatively, if a source of the hydrogel is not available in pure form, the material can be cut from the outsole substrate of a footwear outsole, or from the backing substrate of a coextruded sheet or web, thereby isolating the material. In either case, a 4 cm thick sheet of hydrogel is then cut from the resulting isolated hydrogel. 2 The surface area of the material sample.
[0315] (D)—Pure Material Sampling Procedure
[0316] This procedure can be used to obtain samples of the materials of the present disclosure. In this case, the material is provided in a pure form, such as flakes, granules, powders, pellets, and the like. If a source of the material is not available in a pure form, the material can be cut, scraped, or ground from the outsole of a footwear outsole, or cut from the backing substrate of a coextruded sheet or web, thereby isolating the material.
[0317] Example 2 - Test plan
[0318] The following test procedure is described with reference to outsole components used in articles of footwear, according to the Component Sampling Procedure. However, the same test can be applied to samples used in a simulated environment (e.g., using samples prepared according to the Coextruded or Laminated Film Sampling Procedure, the Pure Film Sampling Procedure, or the Pure Material Sampling Procedure). In other words, measurements obtained on a pure material can be attributed to an outsole comprising the material, wherein the material defines at least a portion of a surface or side of the outsole. In addition, measurements made in a simulated environment can be used to select desired performance attributes of an outsole comprising the material, wherein the material defines at least a portion of a surface or side of the outsole.
[0319] (I)—Water absorption capacity test plan
[0320] This test measures the water absorption capacity of a sample (e.g., obtained using the component sampling procedure described above) after a predetermined soaking duration. The sample is initially dried at 60°C until there is no weight change for consecutive measurement intervals of at least 30 minutes apart (e.g., a 24 hour drying period at 60°C is typically a suitable duration). The total weight (Wt ,干样品 ) is measured in grams. The dried sample is allowed to cool to 25°C and completely immersed in a deionized water bath maintained at 25°C. After a given immersion duration, the sample is removed from the deionized water bath, blotted with a cloth to remove surface water, and the total weight of the immersed sample is measured in grams (Wt, 湿样品 ).
[0321] Any suitable soaking duration may be used, with a soaking duration of 24 hours being considered to simulate the saturation conditions of the thermoplastic hydrogels of the present disclosure (i.e., the hydrophilic thermoplastic hydrogel will be in its saturated state). Thus, as used herein, the phrase "having a water absorption capacity at 5 minutes" refers to a soaking duration of 5 minutes, the phrase "having a water absorption capacity at 1 hour" refers to a soaking duration of 1 hour, the phrase "having a water absorption capacity at 24 hours" refers to a soaking duration of 24 hours, and the like.
[0322] As will be appreciated, the total weight of the sample collected in accordance with the component sampling procedure includes the weight of the material when dry or soaked (Wt ,干样品 or Wt ,湿样品 ), and the backing material substrate (Wt ,基底 )’s weight.
[0323] The weight of the substrate (Wt ,基底 ) using a sample surface area (e.g., 4.0 cm 2), the average measured thickness of the backing substrate in the sample and the average density of the backing substrate material. Alternatively, if the density of the backing substrate material is unknown or unavailable, the weight of the substrate (Wt ,基底 ) is determined by collecting a second sample using the same sampling procedure used for the original sample and having the same dimensions (surface area and film / substrate thickness) as the original sample. The material of the second sample is then cut away from the substrate of the second sample with a razor blade to provide a separated substrate. The separated substrate is then dried at 60°C for 24 hours, which can be done simultaneously with the drying of the original sample. The weight of the separated backing substrate is then measured in grams (Wt ,基底 ).
[0324] Then the weight of the original sample (Wt ,干样品 or Wt ,湿样品 ) minus the weight of the backing substrate (Wt ,基底 ) to provide the weight of the dry and soaked material (Wt ,干部件 or Wt ,湿部件 ), as shown in Equation 1 and Equation 2.
[0325] Wt 干部件 =Wt ,干样品 -Wt ,基底
[0326] (Equation 1)
[0327] Wt 湿部件 =Wt ,湿样品 -Wt ,基底
[0328] (Equation 2)
[0329] The weight of the dried part (Wt. 干部件 ) from the weight of the immersed part (Wt 湿部件 ) to provide the weight of water absorbed by the part, which is then divided by the weight of the dry part (Wt. 干部件 ), provides the water absorption capacity for a given soaking duration in percentage form, as shown in Equation 3 below.
[0330]
[0331] For example, a water absorption capacity of 50% at 1 hour means that the weight of the soaked component after immersion for 1 hour is 1.5 times its dry weight. Similarly, a water absorption capacity of 500% at 24 hours means that the weight of the soaked component after immersion for 24 hours is six times its dry weight.
[0332] (II)—Water absorption rate test plan
[0333] This test measures the rate of water absorption by a hydrogel by modeling the weight gain as a function of the sample's immersion time using a one-dimensional diffusion model. Samples may be collected using any of the sampling procedures discussed above, including the component sampling procedure. The sample is dried at 60°C until there is no weight change for consecutive measurement intervals of at least 30 minutes apart (a 24 hour drying period at 60°C is typically a suitable duration). The total weight (Wt ,干样品 ) is measured in grams. In addition, the average thickness of the parts of the dried samples was measured for use in calculating the water absorption rate, as explained below.
[0334] The dried samples were allowed to cool to 25° C. and completely immersed in a deionized water bath maintained at 25° C. Between immersion durations of 1 minute, 2 minutes, 4 minutes, 9 minutes, 16 minutes, and 25 minutes, the samples were removed from the deionized water bath, blotted with a cloth to remove surface water, and the total weight of the immersed samples (Wt) was measured in grams. ,湿样品 ), where "t" refers to a specific soak duration data point (e.g., 1 minute, 2 minutes, 4 minutes, 9 minutes, 16 minutes, or 25 minutes).
[0335] The exposed surface area of the immersed sample was also measured with a caliper for determination of specific weight gain, as explained below. The exposed surface area refers to the surface area in contact with deionized water when fully immersed in the bath. For samples obtained using the component sampling procedure, the sample had only one major surface exposed. For convenience, the surface area of the peripheral edge of the sample was ignored due to its relatively small size.
[0336] Between measurements, the sample under test was fully immersed back into the deionized water bath. The durations of 1 minute, 2 minutes, 4 minutes, 9 minutes, 16 minutes, and 25 minutes refer to the cumulative immersion duration of the sample fully immersed in the deionized water bath (i.e., after the first minute of immersion and the first measurement, the sample was returned to the bath for an additional minute of immersion before being measured at the 2 minute mark).
[0337] As mentioned above, in the water absorption capacity test, the total weight of the sample collected according to the component sampling procedure includes the weight of the dry or soaked material (Wt 湿部件 or Wt. 干部件 ) and the weight of the article or backing substrate (Wt ,基底 To determine the weight change of a material due to water absorption, the weight of the backing substrate (Wt ,基底 This can be done using the same steps discussed above in the Water Absorption Capacity Test to provide the resulting material weight Wt for each soak duration measurement.,湿部件 and Wt .干部件 .
[0338] The specific weight gain (Ws) from water absorption of each soaked sample was then t ) is calculated as the weight of the immersed sample (Wt 湿部件 ) and the weight of the initial dried sample (Wt .干部件 ), where the difference is then divided by the exposed surface area (A t ), as shown in Equation 4.
[0339]
[0340] Where t refers to a specific soak duration data point (e.g., 1 minute, 2 minutes, 4 minutes, 9 minutes, 16 minutes, or 25 minutes), as described above.
[0341] Then, the water uptake rate of the hydrogel was determined as the specific weight gain (Ws t ) versus the square root of time (in minutes), as determined by least squares linear regression of the data points. For the hydrogels of the present disclosure, specific weight gain (Ws t ) versus the square root of time (in minutes) provides a substantially linear initial slope (to provide the water absorption rate by linear regression analysis). However, after a period of time that depends on the thickness of the component, the specific weight gain will slow, indicating a decrease in the water absorption rate until saturation is reached. This is believed to be due to the water being fully diffused throughout the hydrogel as water absorption approaches saturation, and will vary depending on component thickness.
[0342] Thus, for parts having an average thickness of less than 0.3 mm (as measured above), only the specific weight gain data points at 1 minute, 2 minutes, 4 minutes, and 9 minutes were used in the linear regression analysis. In these cases, the data points at 16 minutes and 25 minutes may begin to deviate significantly from the linear slope due to water absorption approaching saturation, and are omitted from the linear regression analysis. In contrast, for parts having an average dry thickness of 0.3 mm or greater (as measured above), the specific weight gain data points at 1 minute, 2 minutes, 4 minutes, 9 minutes, 16 minutes, and 25 minutes are used in the linear regression analysis. The resulting slope defining the water absorption rate of the sample has units of weight / (surface area-square root of time), for example, grams / (meters). 2 -minute 1 / 2 ) or g / m 2 / √min.
[0343] In addition, some component surfaces can produce surface phenomena that quickly attract and retain water molecules (e.g., via surface hydrogen bonding or capillary action) without actually pulling the water molecules into the membrane or substrate. Therefore, samples of these membranes or substrates can show a rapid specific weight gain for the 1 minute sample, and possibly for the 2 minute sample. However, after that, further weight gain is negligible. Therefore, the linear regression analysis is only applicable if the specific weight gain of the data points at 1 minute, 2 minutes, and 4 minutes continues to show an increase in water absorption. If this is not the case, the water absorption rate under this test method is considered to be approximately zero g / m 2 / √min.
[0344] (III)—Swelling capacity test scheme
[0345] This test measures the swelling capacity of a part in terms of the increase in thickness and volume of a sample (e.g., obtained using the part sampling procedure discussed above) after a given immersion duration. The sample is initially dried at 60°C until there is no weight change for consecutive measurement intervals of at least 30 minutes apart (a 24 hour drying period is typically a suitable duration). The dimensions of the dried sample are then measured (e.g., thickness, length, and width for rectangular samples; thickness and diameter for circular samples, etc.). The dried sample is then completely immersed in a deionized water bath maintained at 25°C. After a given immersion duration, the sample is removed from the deionized water bath, blotted with a cloth to remove surface water, and the same dimensions of the immersed sample are measured again.
[0346] Any suitable soaking duration may be used. Thus, as used herein, the phrase "having a swollen thickness (or volume) increase at 5 minutes" refers to a soaking duration of 5 minutes, the phrase "having a swollen thickness (or volume) increase at 1 hour" refers to a test duration of 1 hour, the phrase "having a swollen thickness (or volume) increase at 24 hours" refers to a test duration of 24 hours, and similar.
[0347] The swelling of the part is determined by: (1) the increase in thickness between the dry part and the soaked part, (2) the increase in volume between the dry part and the soaked part, or (3) both. The increase in thickness between the dry part and the soaked part is calculated by subtracting the measured thickness of the initial dry part from the measured thickness of the soaked part. Similarly, the increase in volume between the dry part and the soaked part is calculated by subtracting the measured volume of the initial dry part from the measured volume of the soaked part. The increase in thickness and volume can also be expressed as a percentage increase relative to the dry thickness or dry volume, respectively.
[0348] (IV)—Contact angle test
[0349] The test measures the contact angle of a sample surface (e.g., the surface of a shoe outsole of the present disclosure, wherein the surface is defined by a hydrogel of the present disclosure; or the surface of a coextruded film formed from a hydrogel; or the surface of a pure film formed from a hydrogel) based on a static sessile drop contact angle measurement of a sample (e.g., obtained using the component sampling procedure, the coextruded or laminated film sampling procedure, or the pure film sampling procedure discussed above). The contact angle refers to the angle at which the liquid interface meets the solid surface of the sample and is an indicator of how hydrophilic the surface is.
[0350] For dry testing (i.e., determination of dry contact angle), the samples were initially equilibrated at 25° C. and 20% humidity for 24 hours. For wet testing (i.e., determination of wet contact angle), the samples were completely immersed in a deionized water bath maintained at 25° C. for 24 hours. After this, the samples were removed from the bath, blotted with a cloth to remove surface water, and clamped on a glass slide if necessary to prevent curling.
[0351] The dry or wet sample is then placed on the moveable stage of a contact angle goniometer, such as a commercially available goniometer under the trade name "RAME-HART F290" from Rame-Hart Instrument Co., Succasunna, NJ. A 10 microliter drop of deionized water is then placed on the sample using a syringe and an automated pump. An image of the drop is then taken immediately (before the material can absorb the drop), and the contact angles of the two edges of the drop are measured from the image. The reduction in contact angle between the dry and wet samples is calculated by subtracting the measured contact angle of the wet material from the measured contact angle of the dry material.
[0352] (V)—Friction coefficient test
[0353] This test measures the coefficient of friction of a sample surface (e.g., a surface of a shoe outsole according to the present disclosure, a surface of a coextruded film formed from a hydrogel of the present disclosure, or a surface of a neat film formed from a hydrogel of the present disclosure) of a sample (e.g., obtained using the component sampling procedure, the coextruded or laminated film sampling procedure, or the pure material sampling procedure discussed above). For dry testing (i.e., determining the dry coefficient of friction), the sample is initially equilibrated at 25° C. and 20% humidity for 24 hours. For wet testing (i.e., determining the wet coefficient of friction), the sample is completely immersed in a deionized water bath maintained at 25° C. for 24 hours. After this, the sample is removed from the bath and blotted with a cloth to remove surface water.
[0354] The measurements were made with an aluminum sled mounted on an aluminum test track, which was used to perform sliding friction tests on the sample by sliding the sample on the aluminum surface of the test track. The test track measured 127 mm wide by 610 mm long. The aluminum sled measured 76.2 mm by 76.2 mm, with the leading edge cut to have a 9.5 mm radius. The contact area of the aluminum sled with the track was 76.2 mm by 66.6 mm, or 5,100 square mm).
[0355] Dry or wet samples were attached to the bottom of the sled using a room temperature curing two-component epoxy adhesive commercially available under the trade name "LOCTITE 608" from Henkel, Düsseldorf, Germany. The adhesive was used to maintain the planarity of the wet samples, which may curl when saturated. Polystyrene foam having a thickness of approximately 25.4 millimeters was attached to the top surface of the sled (opposite the test sample) for structural support.
[0356] The sliding friction test is carried out using a screw-driven load frame. The tow cable is attached to the skid using a mount supported in a polystyrene foam structural support, and is wound around a pulley to drag the skid over an aluminum test track. The sliding force or friction force is measured using a load transducer with a capacity of 2000 Newtons. The normal force is controlled by placing a weight on the top of an aluminum skid supported by a polystyrene foam structural support, and the total weight of the skid is 20.9 kilograms (205 Newtons). The crosshead of the test frame increases at a speed of 5 mm / sec, and the total test displacement is 250 mm. The friction coefficient is calculated based on the steady-state force parallel to the direction of motion required to tow the skid at a constant speed. The friction coefficient itself is obtained by dividing the steady-state pulling force by the applied normal force. Any transient value associated with the static friction coefficient at the beginning of the test will be ignored.
[0357] (VI)—Storage modulus test
[0358] This test measures the resistance (ratio of stress to strain) of a sample of a material (e.g., a hydrogel) to deformation when a vibratory force or oscillating force is applied to it, and is a good indicator of the compliance of the hydrogel in both dry and wet states. For this test, the sample is provided in film form using a pure film sampling procedure modified so that the surface area of the test sample is rectangular and has dimensions of 5.35 mm wide and 10 mm long. The material thickness can range from 0.1 mm to 2 mm, and the specific range is not particularly limited because the final modulus result is normalized according to the material thickness.
[0359] The storage modulus (E') of the samples in megapascals (MPa) was determined by dynamic mechanical analysis (DMA) using a commercially available DMA analyzer under the trade designation "Q800 DMAANALYZER" from TA Instruments, New Castle, DE, equipped with a relative humidity accessory to maintain the samples at a constant temperature and relative humidity during analysis.
[0360] Initially, the thickness of the test sample was measured using a caliper (for use in modulus calculations). The test sample was then clamped into a DMA analyzer that was operated under the following stress / strain conditions during analysis: isothermal temperature was 25° C., frequency was 1 Hz, strain amplitude was 10 microns, preload was 1 Newton, and force track was 125%. DMA analysis was performed at a constant temperature of 25° C. according to the following time / relative humidity profile: (i) 0% RH for 300 minutes (representing the dry state for storage modulus determination), (ii) 50% RH for 600 minutes, (iii) 90% RH for 600 minutes (representing the wet state for storage modulus determination), and (iv) 0% RH for 600 minutes.
[0361] At the end of each time period with a constant RH value, the E' value (in MPa) is determined from the DMA curve according to standard DMA techniques. That is, in a specified time / relative humidity profile, the E' value at 0% RH (i.e., the dry storage modulus) is the value at the end of step (i), the E' value at 50% RH is the value at the end of step (ii), and the E' value at 90% RH (i.e., the wet storage modulus) is the value at the end of step (iii).
[0362] A material sample can be characterized by its dry storage modulus, wet storage modulus, or a decrease in storage modulus between a dry material and a wet material, wherein the wet storage modulus is less than the dry storage modulus. This decrease in storage modulus can be listed as the difference between the dry storage modulus and the wet storage modulus, or as a percentage change relative to the dry storage modulus.
[0363] (VII)—Glass transition temperature test
[0364] The glass transition temperature can be determined according to the test method detailed in ASTM D3418-97 Standard Test Method for Transition Temperature and Enthalpy of Melting and Crystallization of Polymers by Differential Scanning Calorimetry, which is consistent with the description herein. The test measures the glass transition temperature (T g ), wherein the hydrogel is provided in pure form, for example, using a pure film sampling procedure or a pure material sampling procedure, with a sample weight of 10 mg. The samples are measured in both dry and wet states (i.e., after exposure to a humid environment as described herein).
[0365] The glass transition temperature was determined using DMA using a commercially available DMA analyzer from TA Instruments, New Castle, DE, under the trade name "Q2000 DMA ANALYZER", equipped with an aluminum sealed pan with a pinhole cover, and the sample chamber was purged with 50 ml / min of nitrogen during the analysis. The dry samples were prepared by holding at 0% RH until constant weight (less than 0.01% weight change over a 120 minute period). The wet samples were prepared by conditioning at a constant 25°C according to the following time / relative humidity (RH) profile: (i) 250 minutes at 0% RH, (ii) 250 minutes at 50% RH, and (iii) 1,440 minutes at 90% RH. The conditioning procedure of step (iii) can be terminated early if the sample weight is measured during conditioning and is measured to be substantially constant within 0.05% during a 100 minute time interval.
[0366] After preparing the sample in dry or wet state, the sample was analyzed by differential scanning calorimetry (DSC) to provide a heat flow versus temperature curve. The DSC analysis was performed using the following time / temperature profile: (i) equilibration at -90°C for 2 minutes, (ii) ramping to 250°C at +10°C / min, (iii) ramping down to -90°C at -50°C / min, and (iv) ramping to 250°C at +10°C / min. The glass transition temperature value (in degrees Celsius) was determined from the DSC curve according to standard DSC techniques.
[0367] (VIII) Melt flow index test.
[0368] Melt flow index is determined according to the test method of procedure A described in detail in ASTM D1238-13 standard test method for melt flow rate of thermoplastics by extrusion plastograph. In short, melt flow index measures the rate at which thermoplastics are extruded through a hole at a specified temperature and load. In the test method, approximately 7 grams of material are loaded into the barrel of a melt flow apparatus, which has been heated to a temperature specified for the material. The weight specified for the material is applied to the plunger, and the molten material is forced through the die. The timed extrudate is collected and weighed. The melt flow value is calculated in g / 10min.
[0369] (IX) Flexure test of cold sole materials.
[0370] The cold sole material flexure test is determined according to the following test method. The purpose of this test is to evaluate the crack resistance of the sample when it is repeatedly flexed to 60 degrees in a cold environment. The thermoformed substrate of the material used for the test is sized to fit inside the flexure test machine. Each material is tested as five separate samples. The flexure test machine is capable of flexing the sample to 60 degrees at a rate of 100 + / - 5 cycles per minute. The mandrel diameter of the machine is 10 mm. Machines suitable for this test are Emerson AR-6, Satra S Tm 141F, Gotech GT-7006 and Shin II Scientific SI-LTCO (DaeSungScientific). According to the specific parameters of the flexure machine used, the sample is inserted into the machine. The machine is placed in a freezer set to -6°C for testing. The motor is turned on to start flexure, and the flexure cycles are counted until the sample cracks. The cracking of the sample means that the surface of the material is physically separated. Visible creases that do not actually penetrate the line of the surface are not cracking. The sample is measured to the extent that it has cracked but has not yet split into two.
[0371] (X) Modulus test.
[0372] According to the test method detailed in the ASTM D412-98 standard test method for vulcanized rubber, thermoplastic rubber and thermoplastic elastomer-tension, the modulus for the thermoforming substrate of the material has been determined, and the following modifications have been made. The sample size is ASTM D412-98 Die C, and the sample thickness used is 2.0 mm + / - 0.5 mm. The type of fixture used is a pneumatic fixture with a metal serrated grip face. The fixture distance used is 75 mm. The loading rate used is 500 mm / min. Modulus (initial) is calculated by taking the slope of the stress (MPa) relative strain in the initial linear region.
[0373] In this specification, embodiments have been described in a manner that enables a clear and concise description to be written, but it is intended and will be understood that the embodiments may be combined or separated in various ways without departing from the present invention. For example, it will be appreciated that all preferred features described herein apply to all aspects of the present invention described herein.
[0374] Additional aspects of the composition and properties of hydrogels incorporated into outsoles for forming articles of footwear, as well as additional aspects of other components used in articles of footwear and additional aspects of related test methods and sampling procedures, are described in the following international patent publications: WO 2016 / 033276A1 (International Application No. PCT / US2015 / 047086); WO 2016 / 033274A1 (International Application No. PCT / US2015 / 047084); and WO 2016 / 033271A1 (International Application No. PCT / US2015 / 047081). The entire contents of each of these patent publications are hereby incorporated by reference.
[0375] The foregoing description of various forms of the present invention has been provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the present invention to the precise form disclosed. In light of the above teachings, many modifications or variations are possible. The forms discussed are selected and described to provide the best description of the principles of the present invention and its practical application, so that those of ordinary skill in the art can utilize the present invention in various forms and utilize the present invention using various modifications suitable for the intended specific use. When the appended claims are interpreted according to the extension to which they are fairly, legally and equitably endowed, all such modifications and variations are within the scope of the present invention as determined by the appended claims.
[0376] The present disclosure may be described according to the following numbered items.
[0377] Item 1. A method of manufacturing an outsole component for an article of footwear, the method comprising:
[0378] providing a membrane component comprising a first layer compositionally comprising a polymeric hydrogel material, the first layer defining an outwardly facing surface of the membrane component;
[0379] providing a mold having a molding surface;
[0380] placing the film component into a mold such that a portion of the first layer contacts a portion of the molding surface;
[0381] constraining a portion of the first layer against a portion of the molding surface while loading a second polymeric material into the mold;
[0382] at least partially solidifying the loaded second polymeric material in the mold to produce the outsole component, wherein a portion of the first layer of the membrane component forms an outermost layer of the outsole component; and
[0383] The outsole component is removed from the mold.
[0384] Item 2. The manufacturing method according to Item 1, wherein the step of providing the membrane component includes providing a membrane component having a substantially planar geometry.
[0385] Item 3. The manufacturing method according to Item 1 or 2, wherein the step of providing the film member includes providing an extruded film member.
[0386] Item 4. A manufacturing method according to any one of Items 1-3, wherein the step of providing the film component includes providing a film component comprising a layered film, the layered film comprising a backing layer operably connected to the first layer, the backing layer comprising a third polymer material in composition.
[0387] Item 5. A manufacturing method according to any one of Items 1-4, wherein the step of placing the film component into the mold so that a portion of the first layer contacts a portion of the molding surface includes placing the film component into the mold so that the first layer contacts a portion of the molding surface that is less than 85% of the total molding surface area of the mold.
[0388] Item 6. A manufacturing method according to any one of Items 1-5, wherein the method includes maintaining the film part at a temperature in the range of about 10°C (C) to about 80°C, except when the second polymer material is loaded into the mold, after the second polymer material is loaded into the mold, and when the loaded second polymer material is at least partially solidified in the mold.
[0389] Item 7. The manufacturing method according to any one of Items 1 to 6, wherein the step of providing the film component includes providing the third polymer material;
[0390] providing the polymer hydrogel material;
[0391] forming the layered film from the polymer hydrogel material and the third polymer material using a co-extrusion process or a lamination process; and
[0392] The layered film is cut to form the film member.
[0393] Item 8. A manufacturing method according to any one of Items 1-7, wherein the method further comprises providing a pre-formed traction friction element and adding the pre-formed traction friction element to the mold before loading the second polymer material into the mold.
[0394] Item 9. A manufacturing method according to any one of Items 1-8, wherein the method further comprises providing a preformed accessory for a traction friction element and adding the preformed accessory for a traction friction element to the mold before loading the second polymer material into the mold.
[0395] Item 10. The manufacturing method of any one of Items 1-9, wherein providing the film component includes cutting a film to form the film component, wherein the film component is configured to fit between or around one or more traction friction elements.
[0396] Item 11. The manufacturing method according to Item 9, wherein the step of providing the film member includes die-cutting a film using a flatbed printer or a rotary printer to form the film member.
[0397] Item 12. A manufacturing method according to Item 11, wherein the die cutting step uses a solid engraving die, an adjustable die, a magnetic plate tool, a punching die or a combination thereof.
[0398] Item 13. A manufacturing method according to any one of Items 1-12, wherein the step of providing the membrane component includes: configuring a portion of the membrane to accommodate the adhesion friction elements by cutting one or more holes in a portion of the membrane, or by shaping a portion of the membrane to avoid the one or more adhesion friction elements, or by both cutting and shaping the membrane to be assembled between or around the one or more adhesion friction elements.
[0399] Item 14. The manufacturing method according to any one of Items 1-13, wherein the second polymer material is a thermoplastic polymer material.
[0400] Item 15. The manufacturing method according to any one of Items 1-14, wherein the third polymer material is a thermoplastic polymer material.
[0401] Item 16. A manufacturing method according to any one of Items 1-15, wherein the step of loading the second polymer material into the mold includes closing the mold and injecting the second polymer material into the closed mold using an injection molding process.
[0402] Item 17. A manufacturing method according to any one of Items 1-16, wherein loading the second polymer material into the mold includes loading the second polymer material into the mold, closing the mold before, during or after loading, and applying pressure to the closed mold.
[0403] Item 18. A manufacturing method according to any of Items 1-17, wherein the step of constraining the first layer against the portion of the molding surface includes using a vacuum, using one or more retractable pins, or using both a vacuum and one or more retractable pins.
[0404] Item 19. The method of manufacturing according to any one of Items 1-18, wherein the molding surface is in a predetermined shape of the outsole component.
[0405] Item 20. The method of manufacturing a shoe outsole according to any one of Items 1-19, wherein at least a portion of the molding surface has a predetermined curvature.
[0406] Item 21. A manufacturing method according to any one of Items 1-20, wherein placing the film part into the mold and / or constraining the portion of the first layer of the film part against the portion of the molding surface includes bending or curving the film part to conform to the curvature of the molding surface while maintaining the film part at a temperature in the range of about 10°C to about 80°C.
[0407] Item 22. The method of manufacturing a shoe outsole according to any one of items 1-21, wherein the second polymer material and the third polymer material are substantially identical in composition.
[0408] Item 23. The method of manufacturing a shoe outsole according to any one of items 1-21, wherein the second polymer material and the third polymer material are substantially different in composition from each other.
[0409] Item 24. A manufacturing method according to any one of Items 1-23, wherein the one or more traction friction elements are formed integrally with the outsole component during the molding step; are added separately as snap-fit or screw-on components after the outsole is removed from the mold; or a combination thereof.
[0410] Item 25. The method of manufacturing of any of items 1-24, wherein the one or more traction elements are integrally formed with the outsole component using the second polymer material.
[0411] Item 26. The manufacturing method according to any one of items 1-25, wherein the method further comprises adding a fourth polymer material to the mold;
[0412] Wherein the fourth polymer material is integrally formed into traction elements as part of the outsole component.
[0413] Item 27. The manufacturing method according to Item 26, wherein the fourth polymer material is a thermoplastic polymer material.
[0414] Item 28. A manufacturing method according to any one of Items 26 or 27, wherein the fourth polymer material is substantially the same in composition as the second polymer material.
[0415] Item 29. A manufacturing method according to any one of Items 26 or 27, wherein the fourth polymer material has a higher level of wear resistance than the second polymer material.
[0416] Item 30. The manufacturing method according to any one of Items 1-29, wherein the method further comprises placing the one or more accessories into the mold before adding the second polymer material;
[0417] Wherein the one or more fittings are configured to couple with a snap-fit or screw-on component.
[0418] Item 31. A manufacturing method according to any of Items 1-30, wherein the method further comprises placing one or more pre-formed traction friction element tips into the mold before adding the second polymer material.
[0419] Item 32. A manufacturing method according to any of Items 30 or 31, wherein the snap-fit or screw-on component comprises a material that is compositionally different from the second polymer material.
[0420] Item 33. A method of manufacturing according to any one of Items 1-32, wherein the outsole component includes traction friction elements, and the traction friction elements are lugs, cleats, spikes, sole studs, or a combination thereof.
[0421] Item 34. A method of manufacturing according to any one of items 1-33, wherein the outsole component has a water absorption capacity of greater than 40% by weight at 1 hour as characterized by a water absorption capacity test using a component sampling procedure.
[0422] Item 35. A manufacturing method according to any one of Items 1-34, wherein the outsole component has a thickness greater than 20 g / m 2 The water absorption rate of 100 μl / min as characterized by a water absorption rate test using a component sampling procedure.
[0423] Item 36. A method of manufacturing according to any one of items 1-35, wherein the outsole component has a swollen thickness increase of greater than 20% at 1 hour as characterized by a Swell Capacity Test using a component sampling procedure.
[0424] Item 37. A manufacturing method according to any one of Items 1-36, wherein a component sampling procedure is employed and at least a portion of the outer surface of the outsole component exhibits one or more of a wet contact angle of less than 80° as characterized by a contact angle test and a wet friction coefficient of less than 0.8 as characterized by a friction coefficient test.
[0425] Item 38. The method of manufacturing according to any one of Items 1-37, wherein the polymer hydrogel material exhibits a wet glass transition temperature at equilibrium at 90% relative humidity and a dry glass transition temperature at equilibrium at 0% relative humidity, as characterized by a glass transition temperature test using a pure material sampling process;
[0426] wherein the wet glass transition temperature is more than 6°C lower than the dry glass transition temperature.
[0427] Item 39. The method of manufacturing according to any one of Items 1-38, wherein the polymer hydrogel material has a wet storage modulus at equilibrium at 90% relative humidity and a dry storage modulus at equilibrium at 0% relative humidity, as characterized by a storage modulus test using a pure material sampling procedure;
[0428] wherein the wet storage modulus is less than the dry storage modulus of the polymer hydrogel material.
[0429] Item 40. A manufacturing method according to any one of Items 1-39, wherein the polymer hydrogel material is a thermoplastic hydrogel material.
[0430] Item 41. A manufacturing method according to any one of Items 1-40, wherein the polymer hydrogel material comprises one or more polymers selected from polyurethane, polyamide homopolymer, polyamide copolymer, and any combination thereof.
[0431] Item 42. A manufacturing method according to any one of Items 1-41, wherein the polymer hydrogel material comprises polyurethane.
[0432] Item 43. A manufacturing method according to Item 42, wherein the polyurethane is a thermoplastic polyurethane.
[0433] Item 44. A manufacturing method according to any one of Items 1-43, wherein the polymer hydrogel material comprises a polyamide block copolymer.
[0434] Item 45. The method of manufacturing according to any one of items 1-44, wherein the polymer hydrogel material constitutes at least 80% of the exterior surface of the outsole component.
[0435] Item 46. A manufacturing method according to any one of Items 1-45, wherein the polymer hydrogel material has a dry thickness ranging from 0.1 millimeter (mm) to 2 mm.
[0436] Item 47. A manufacturing method according to any one of Items 1-46, wherein at least one of the second polymer material and the third polymer material comprises one or more natural rubbers or synthetic rubbers.
[0437] Item 48. A manufacturing method according to any one of Items 1-47, wherein the second polymer material and / or the third polymer material further comprises one or more processing aids.
[0438] Item 49. A manufacturing method according to Item 48, wherein the processing aid is independently selected from the following group: curing agent, initiator, plasticizer, release agent, lubricant, antioxidant, flame retardant, dye, pigment, reinforcing filler and non-reinforcing filler, fiber reinforcement and light stabilizer.
[0439] Item 50. A manufacturing method according to any one of Items 1-49, wherein the step of at least partially solidifying the second polymer material includes at least partially cross-linking the second polymer material.
[0440] Item 51. A manufacturing method according to Item 50, wherein the step of at least partially cross-linking the second polymer material comprises using a sulfur-based cross-linking process or a peroxide-initiated cross-linking process to at least partially cross-link the second polymer material.
[0441] Item 52. A manufacturing method according to Item 51, wherein a cross-linking mechanism occurs after the first polymer material and / or the second polymer material is exposed to actinic radiation, and the concentration and duration of the actinic radiation are sufficient to at least partially cure the first polymer material and / or the second polymer material.
[0442] Item 53. The manufacturing method according to any one of Items 1-52, wherein the first polymer material and / or the second polymer material is fully cured.
[0443] Item 54. A shoe outsole component manufactured according to the method of any one of Items 1-53.
[0444] Item 55. A method of manufacturing an article of footwear, the method comprising:
[0445] Providing an outsole component manufactured according to any one of items 1 to 53;
[0446] Providing the upper; and
[0447] The outsole member and the upper are secured to one another such that the polymer hydrogel material of the outsole member defines a ground-facing surface of the article of footwear.
[0448] Item 56. The method according to Item 55, wherein the method further comprises:
[0449] receiving a midsole; and
[0450] Prior to securing the outsole component to the upper, the midsole is attached to the outsole component and / or the upper such that the midsole is located between the outsole component and the upper.
[0451] Item 57. A method according to any one of Items 55 or 56, wherein the upper comprises leather, a thermosetting polymer, a thermoplastic polymer, or a mixture thereof.
[0452] Item 58. A method according to any one of Items 55-57, wherein the upper comprises a textile selected from a knitted textile, a woven textile, a non-woven textile, a braided textile, or a combination thereof.
[0453] Item 59. The method of Item 58, wherein the textile comprises one or more natural or synthetic fibers or yarns.
[0454] Item 60. The method according to Item 59, wherein the synthetic fiber or yarn comprises thermoplastic polyurethane (TPU), polyamide, polyester, polyolefin, or a mixture thereof.
[0455] Item 61. The method of any one of Items 55-60, wherein securing the outsole component to the upper comprises using an adhesive, a primer, or a combination thereof.
[0456] Item 62. An outsole for an article of footwear, comprising an outsole component made according to any of items 1-54.
[0457] Item 63. Use of an outsole component formed according to the method of any one of Items 1-54 in an article of footwear.
[0458] Item 64. An article of footwear manufactured according to any of items 55-61.
[0459] Item 65. Use of an article of footwear formed according to the method of any one of Items 55-61.
[0460] Item 66. An outsole component for an article of footwear, the outsole component comprising:
[0461] a membrane member having a first surface, a second surface opposite the ground-contacting surface, and an outer perimeter, the membrane member compositionally comprising a polymer hydrogel material, the polymer hydrogel material defining the first surface of the membrane member, and at least a portion of the first surface of the membrane member providing at least a portion of the ground-contacting surface of the outsole member;
[0462] a second polymeric material operably attached to the second surface of the film component and the entire outer perimeter of each of the one or more film components; and
[0463] one or more traction elements;
[0464] Wherein the membrane member is fitted between or around the one or more traction friction elements.
[0465] Item 67. An outsole component according to Item 66, wherein the outsole component includes one or more traction friction elements, the one or more traction friction elements have a ground-contacting surface, and the ground-contacting surface of the one or more traction friction elements does not include the membrane component.
[0466] Item 68. The outsole component of Item 66 or 67, wherein the membrane component has a void with an inner perimeter, and the traction friction element passes through the void of the membrane component.
[0467] Item 69. The outsole component of any of Items 66-68, wherein the traction elements include a second polymer material and the second polymer material is operably connected to the inner perimeter of the membrane component.
[0468] Item 70. The outsole component of any of Items 66-69, wherein the second polymer material defines the ground-contacting surface of the traction element.
[0469] Item 71. A method of manufacturing an outsole component for an article of footwear, the method comprising:
[0470] providing a mold having a molding surface;
[0471] placing a film component into the mold, wherein the film component comprises a first outwardly facing surface, the film component comprising a first layer compositionally comprising a polymeric hydrogel material, the first layer defining at least a portion of the first outwardly facing surface of the film component;
[0472] constraining the film member such that at least a portion of the first layer contacts a molding surface to form a constrained film member;
[0473] loading a second polymeric material into the mold having the constrained film member;
[0474] at least partially solidifying the loaded second polymeric material in the mold to produce an outsole component having an outermost surface including at least a portion of the first layer of the membrane component; and
[0475] The outsole component is removed from the mold.
[0476] Item 72. The manufacturing method according to Item 71, further comprising the step of extruding or co-extruding a film comprising the polymer hydrogel material.
[0477] Item 73. A manufacturing method according to Item 71 or 72, wherein the film component also includes a backing layer operably connected to the first layer, and the backing layer compositionally includes a third polymer material.
[0478] Item 74. A manufacturing method according to any one of Items 71-73, wherein the film component is placed or constrained in the mold so that less than 85% of the total molding surface area of the mold is contacted by the film component.
[0479] Item 75. A manufacturing method according to any one of Items 71-74, wherein the method further includes maintaining the film component at a temperature in the range of about 10°C (C) to about 80°C, except during the steps of extruding or co-extruding the film, loading the second polymer material into the mold, and at least partially solidifying the loaded second polymer material in the mold.
[0480] Item 76. The manufacturing method according to Item 73, further comprising:
[0481] providing the third polymer material;
[0482] providing the polymer hydrogel material;
[0483] using a coextrusion process or a lamination process to form a layered film comprising a first layer of a polymeric hydrogel material and a backing layer, the backing layer comprising the third polymeric material; and
[0484] The layered film is cut to form the film member.
[0485] Item 77. A manufacturing method according to any of Items 71-76, wherein the method also includes providing one or more traction friction elements, wherein the one or more traction friction elements are integrally formed with or operably connected to the molded outsole component, or a combination thereof.
[0486] Item 78. A manufacturing method according to Item 77, wherein the method further comprises adding a preformed traction friction element or a preformed accessory for a traction friction element to the mold before loading the second polymer material into the mold.
[0487] Item 79. A manufacturing method according to Item 77 or 78, wherein the membrane component is configured to fit between or around the one or more traction friction elements.
[0488] Item 80. The manufacturing method according to any one of Items 71-79 further includes the following step: die-cutting the film using a flatbed printer, a rotary printer, a solid engraving die, an adjustable mold, a magnetic plate tool, a punching die, or a combination thereof to form the film component.
[0489] Item 81. The manufacturing method according to Item 77 or 78 further includes the following steps: cutting one or more holes or gaps in a portion of the membrane component corresponding to the position of the one or more adhesion friction elements, or forming a portion of the membrane component to avoid the position of one or more adhesion friction elements, or both cutting and forming the membrane component.
[0490] Item 82. A manufacturing method according to any one of Items 71-81, wherein the second polymer material is a thermoplastic polymer material.
[0491] Item 83. A manufacturing method according to Item 73 or 76, wherein the third polymer material is a thermoplastic polymer material.
[0492] Item 84. A manufacturing method according to any of Items 71-83, wherein the step of constraining the first layer against the portion of the molding surface includes using a vacuum, using one or more retractable pins, or using both a vacuum and one or more retractable pins.
[0493] Item 85. A manufacturing method according to any one of Items 71-84, wherein placing the film part in the mold and / or constraining the portion of the first layer of the film part against the portion of the molding surface includes bending or curving the film part to conform to the curvature of the molding surface while maintaining the film part at a temperature in the range of about 10°C to about 80°C.
[0494] Item 86. A manufacturing method according to any one of Items 71-85, wherein the polymer hydrogel material comprises a polymer or copolymer of polyurethane, polyurea, polyester, polycarbonate, polyetheramide, addition polymer of ethylenically unsaturated monomers, and any combination thereof.
Claims
1. A shoe outsole component manufactured according to the following method, the method comprising: providing a mold having a molding surface; placing a film component into the mold, wherein the film component is a pre-cut, planar film component and the film component is not thermoformed after a film of the film component has been formed, wherein the planar film component comprises a first outwardly facing surface, the planar film component comprising a first layer compositionally comprising a polymeric hydrogel material, the first layer defining at least a portion of the first outwardly facing surface of the planar film component; positioning and constraining the planar film member such that at least a portion of the first layer contacts the molding surface to form a constrained film member; maintaining the flat film member at a temperature in the range of 10° C. (C) to 80° C. during at least the steps of placing and restraining the flat film member such that the flat film member is not thermoformed; loading a second polymeric material into the mold having the constrained film member; at least partially solidifying the loaded second polymeric material in the mold to produce the outsole component, the outsole component having an outermost surface including at least a portion of the first layer of the membrane component; as well as The outsole component is removed from the mold.
2. The outsole component of claim 1, wherein the method further comprises the step of extruding or coextruding a flat film component comprising the polymer hydrogel material.
3. The outsole component of claim 1, wherein the planar membrane component further comprises a backing layer operably connected to the first layer, the backing layer compositionally comprising a third polymeric material.
4. The outsole component of claim 1, the planar membrane component being positioned or restrained in the mold such that less than 85% of the total molding surface area of the mold is contacted by the planar membrane component.
5. The outsole component of claim 1 , wherein the method further comprises maintaining the flat membrane component at a temperature in the range of 10° C. to 80° C. except during the steps of loading the second polymer material into the mold and at least partially solidifying the loaded second polymer material in the mold.
6. The outsole component of claim 3, wherein the method further comprises: providing the third polymer material; providing the polymer hydrogel material; forming a layered film comprising a first layer of a polymer hydrogel material and a backing layer comprising the third polymer material using a coextrusion process or a lamination process; and The layered film is cut to form the flat film member.
7. The outsole component of claim 1, wherein the method further comprises providing one or more traction elements integrally formed with or operably coupled to the molded outsole component, or a combination thereof.
8. The outsole component of claim 7, wherein the method further comprises adding pre-formed traction elements or pre-formed accessories for traction elements to the mold prior to loading the second polymer material into the mold.
9. The outsole component of claim 7, wherein the planar membrane component is configured to fit between or around the one or more traction elements.
10. The outsole component of claim 1, wherein the method further comprises the step of die cutting a film using a flatbed printer, a rotary printer, a solid engraved die, an adjustable die, a magnetic plate tool, a punch die, or a combination thereof to form the film component.
11. The outsole component of claim 7, wherein the method further comprises the steps of: One or more holes or voids are cut in a portion of the planar film member corresponding to the location of the one or more traction elements, or a portion of the planar film member is shaped to avoid the location of the one or more traction elements, or both.
12. The outsole component of claim 1, wherein the second polymer material is a thermoplastic polymer material.
13. The outsole component of claim 3, wherein the third polymer material is a thermoplastic polymer material.
14. The outsole component of claim 1, wherein the step of constraining the portion of the first layer against the molding surface comprises using a vacuum, using one or more retractable pins, or using both a vacuum and one or more retractable pins.
15. The outsole component of claim 1 , wherein placing the flat film component in the mold and / or constraining a portion of the first layer of the flat film component against a portion of the molding surface includes bending or flexing the flat film component to conform to the curvature of the molding surface while maintaining the flat film component at a temperature in the range of 10° C. to 80° C.
16. The outsole component of claim 1, wherein the polymer hydrogel material comprises a polymer or copolymer of polyurethane, polyurea, polyester, polycarbonate, polyetheramide, addition polymer of ethylenically unsaturated monomers, and any combination thereof.
17. The outsole component according to any one of claims 1-8 and 10-16, wherein the outsole component comprises: The surface that touches the ground; at least one planar membrane member having a first surface, a second surface opposite the first surface, and an outer perimeter, the planar membrane member compositionally comprising a polymer hydrogel material defining at least a portion of the first surface of the planar membrane member and at least a portion of the ground-contacting surface of the outsole member; a second polymeric material operably attached to the second surface of the planar membrane member and to the entire outer perimeter of each of the one or more planar membrane members; as well as one or more traction elements; Wherein the at least one planar membrane member fits between or around the one or more traction friction elements.
18. The outsole component of claim 17, wherein the one or more traction elements include a ground-contacting surface, and the ground-contacting surface of the one or more traction elements is free of the polymer hydrogel material of the planar membrane component.
19. An article of footwear comprising an outsole element according to any one of claims 1-18.
Citation Information
Patent Citations
Medical dressing and negative pressure wound therapy apparatus using the same
EP2462908A1
Thermoplastic silicone-containing hydrogels
US5969076A
Article of footwear with soil-shedding performance
WO2016033271A2
Article of footwear with soil-shedding performance
WO2016033276A1
Outsole for articles of footwear with water absorbant ground contacting surface
WO2016033274A1